Lithium ion secondary battery, preparation method and electric device
By using chain carboxylic acid ester compounds and specific additives in the electrolyte of lithium-ion secondary batteries, a stable SEI film is formed, which solves the problems of interface side reactions and gas production during fast charging, and achieves better fast charging performance and cycle life.
Patent Information
- Application Number
- CN202510378403.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2025-04-29
AI Technical Summary
During the fast charging process, lithium-ion secondary batteries are prone to interface side reactions and gas production problems, resulting in a degradation of circulation performance and limiting the development of the fast charging system.
An electrolyte containing chain carboxylic acid ester compounds and specific additives is used to introduce non-ionic alkyne organic additives and negative electrode film-forming additives into the negative electrode sheet to form a stable solid electrolyte interface (SEI) film to inhibit interface side reactions and gas production.
It significantly improves the fast charging performance of lithium-ion secondary batteries, extends the cycle life of the fast charging battery system, and reduces the internal resistance of the battery.
Smart Images

Figure CN119905665A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion secondary batteries, and further to lithium-ion secondary batteries, preparation methods and electrical devices. Background Art
[0002] The statements herein merely provide background information related to the present application and do not necessarily constitute prior art.
[0003] With the development of lithium-ion secondary battery technology, lithium-ion secondary batteries are increasingly widely used in smart phones, tablet computers, laptops, power tools, electric bicycles, electric motorcycles, electric vehicles, aerospace and other fields. They are also widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations. The fast charging capability of lithium-ion secondary batteries has attracted much attention. However, the fast charging system of lithium-ion secondary batteries usually faces the problem of gas production. The interfacial side reactions accompanied by gas production will deteriorate the cycle performance of the fast charging battery, restricting the further development of the fast charging system. Summary of the invention
[0004] According to various implementations and examples of the present application, the present application provides a lithium ion secondary battery, a preparation method and an electrical device. The lithium ion secondary battery has improved fast charging performance and can extend the cycle life of the fast charging battery system.
[0005] In some embodiments of the first aspect of the present application, a lithium ion secondary battery is provided, which includes a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein a separator is provided between the positive electrode sheet and the negative electrode sheet; the electrolyte includes an electrolyte salt, a non-aqueous solvent and an additive; the non-aqueous solvent includes a chain carboxylate compound, the chain carboxylate compound includes a solvent of formula I, and the structure of the solvent of formula I is shown in formula (I): In formula (I), R 11 and R 12 are each independently methyl or ethyl;
[0006] The additives include a first additive and a second additive, wherein the first additive is a non-ionic organic additive containing a carbon-carbon triple bond, and the second additive is a negative electrode film-forming additive different from the first additive.
[0007] The "first additive" used in the present application is a non-ionic organic additive containing a carbon-carbon triple bond, which is a non-ionic acetylene organic additive. It can be understood that the additive in the electrolyte includes an acetylene additive.
[0008] The lithium-ion secondary battery introduces a non-ionic acetylene organic additive (referred to as the first additive) and a second additive (a negative electrode film-forming additive different from the first additive) when using a highly conductive solvent.11 and R 12 All of them have a small number of carbon atoms, which makes the solvent of formula I have a lower viscosity and a higher conductivity; secondly, the first additive can participate in the formation and repair of the solid electrolyte interface (SEI) film at the negative electrode, which can significantly improve the stability of the SEI film, thereby significantly inhibiting the interfacial side reactions between the negative electrode and the electrolyte during the fast charging process, and the problem of the solvent of formula I being easily decomposed and producing gas is significantly inhibited; thirdly, the second additive can competitively participate in the film formation at the negative electrode, which can reduce or delay the consumption of the first additive in the film formation at the negative electrode, and can inhibit the increase in the negative electrode interface impedance caused by the participation of the first additive in the film formation at the negative electrode; based on the synergy of the aforementioned effects, but not limited to the aforementioned theory, the lithium-ion secondary battery has an improved fast charging performance, including extending the cycle life of the fast charging battery system.
[0009] In some embodiments, the linear carboxylic acid ester compound includes one or more of methyl formate, ethyl formate, methyl acetate and ethyl acetate.
[0010] In some embodiments, the negative electrode plate includes a negative electrode active layer, the negative electrode active layer includes a negative electrode active material, and the average particle size of primary particles in the negative electrode active material is denoted as D1, wherein D1 is 0.1 μm~2 μm, and can be optionally 0.5 μm~1.2 μm.
[0011] By controlling the average particle size of the primary particles in the negative electrode active material (denoted as D1) within the aforementioned range, it is possible to control the negative electrode active material to have a more suitable ion transmission path and achieve a better rate, and at the same time, better control the negative electrode interface reaction, control the negative electrode film consumption of the first additive, better optimize the SEI film and inhibit gas production. Based on the synergy of the aforementioned effects, but not limited to the aforementioned theory, it is beneficial to better control the internal resistance of the battery and to enable the lithium-ion secondary battery to achieve better fast charging performance.
[0012] In some embodiments, the D of the negative electrode active material v 50 is 5μm~18μm.
[0013] In some embodiments, the D of the negative electrode active material v 50 is 6μm~15μm.
[0014] By increasing the D v50 is controlled within the aforementioned range, the specific surface area of the negative electrode active material can be controlled within a relatively low range, which is beneficial to reducing the negative electrode interface side reactions, reducing or delaying the negative electrode interface consumption of the first additive, optimizing the SEI film and inhibiting gas production during fast charging, and is also beneficial to better control the overall ion transmission path of the negative electrode active material particles. Based on the synergy of the aforementioned effects, but not limited to the aforementioned theory, it is beneficial to better control the battery internal resistance and to enable the lithium-ion secondary battery to achieve better fast charging performance.
[0015] By increasing the D v 50 is controlled within the aforementioned range and can be matched with a relatively small average primary particle size.
[0016] By synergistically controlling the D v 50 and the average particle size of the primary particles in the negative electrode active material, which is beneficial to take into account the ion transmission path of the primary particles and the particles as a whole in the negative electrode active material, and at the same time better inhibit the negative electrode interface side reaction and inhibit gas production. Based on the synergy of the above-mentioned effects, but not limited to the above-mentioned theory, it is beneficial to better control the internal resistance of the battery and to enable the lithium-ion secondary battery to achieve better fast charging performance.
[0017] In some embodiments, the negative electrode active material includes a coated negative electrode material, wherein the coated negative electrode material includes a negative electrode active body and a carbon coating layer located on at least a portion of the negative electrode active body.
[0018] In some embodiments, the negative electrode plate satisfies one or more of the following characteristics:
[0019] (a1) The mass proportion of the coated negative electrode material in the negative electrode active material is 80% to 100%;
[0020] (a2) The coated negative electrode material includes coated graphite, the negative electrode active body in the coated graphite includes a graphite body, and the coated graphite accounts for 80% to 100% by mass of the negative electrode active material.
[0021] By providing a coated negative electrode material (such as coated graphite) including a carbon coating layer in the negative electrode active material, the lithium ion transmission channel on the surface of the negative electrode active material can be optimized, lithium ion transmission can be promoted, and the dynamics of the lithium ion secondary battery can be improved. At the same time, it is also beneficial to inhibit the negative electrode interface side reactions and inhibit the increase in interface impedance caused by the participation of the first additive in film formation, which is beneficial to better improve the fast charging performance of the lithium ion secondary battery.
[0022] By providing a coated negative electrode material including a carbon coating layer (such as coated graphite) in the negative electrode active material, the rate performance can be optimized by combining a relatively small average primary particle size.
[0023] In some embodiments, the positive electrode plate includes a positive electrode active layer, and the positive electrode active layer includes a positive electrode active material; the positive electrode active material includes one or more of a lithium-containing phosphate positive electrode material and a lithium transition metal oxide positive electrode material;
[0024] The positive electrode sheet meets one or more of the following characteristics:
[0025] (b1) The positive electrode active material includes a lithium-containing phosphate positive electrode material, and the D of the lithium-containing phosphate positive electrode material v 50: 0.3μm~2μm;
[0026] (b2) The positive electrode active material includes a lithium transition metal oxide positive electrode material, and the D of the lithium transition metal oxide positive electrode material v 50 is 2μm~10μm.
[0027] By controlling the type of positive electrode active material and the aforementioned D v 50, which is conducive to better coordination between the lithium ion extraction kinetics of the positive electrode and the lithium insertion kinetics of the negative electrode, which is conducive to reducing the internal resistance of the battery and better improving the fast charging performance.
[0028] In some embodiments, the negative electrode plate includes a negative electrode active layer, and the negative electrode active layer includes a negative electrode active material; the positive electrode plate includes a positive electrode active layer, and the positive electrode active layer includes a positive electrode active material;
[0029] (c1) D of the negative electrode active material v 1 greater than or equal to 1.5 μm;
[0030] (c2) The positive electrode active material includes a lithium transition metal oxide positive electrode material, and the D of the lithium transition metal oxide positive electrode material v 10 greater than or equal to 1 μm;
[0031] (c3) The positive electrode active material comprises a lithium-containing phosphate positive electrode material, and the D v 10 is greater than or equal to 0.2 μm.
[0032] By controlling the D v 1. D of positive electrode active material v Controlling one or both of 10 within the aforementioned range is beneficial to reducing the content of smaller particles with extremely small size and extremely large specific surface area at the negative electrode and / or the positive electrode, which is beneficial to better inhibiting the interface side reactions of the negative electrode and / or the positive electrode, and better inhibiting fast charging and gas production.
[0033] By controlling the D v1 Within the aforementioned range, the negative electrode interface side reaction can be significantly inhibited, the consumption rate of the first additive can be reduced, and the battery internal resistance growth rate can be reduced, which is conducive to maintaining a better fast charging performance for a longer period of time.
[0034] The first additive can adsorb transition metal ions in the electrolyte. v 10 Within the aforementioned range, it is beneficial to better control the dissolution of transition metal ions in the positive electrode, so that the first additive can participate more in the formation and repair of the negative electrode interface film, which is beneficial to maintain better fast charging performance for a longer period of time.
[0035] By controlling the D v 10 Within the aforementioned range, it is beneficial to better control the water content of the positive electrode active material, thereby helping to reduce acid byproducts (such as hydrofluoric acid), and further helping to improve the stability of the negative electrode interface and the negative electrode active material, helping to reduce the consumption rate of the first additive, reducing the battery internal resistance growth rate, and helping to maintain a better fast charging performance for a longer period of time.
[0036] In some embodiments, the negative electrode plate includes a negative electrode active layer, and the negative electrode active layer includes a negative electrode active material; the negative electrode active material includes at least one of a carbon-based material and a silicon-based material, and the mass proportion of the silicon-based material in the negative electrode active material is 0~40%.
[0037] In some embodiments, the negative electrode plate satisfies one or more of the following characteristics:
[0038] (d1) The mass proportion of the silicon-based material in the negative electrode active material is 0-25%;
[0039] (d2) The silicon-based material includes a silicon-carbon composite material, which includes a porous carbon matrix and elemental silicon located in the pores of the porous carbon matrix; the mass proportion of the silicon-carbon composite material in the silicon-based material is 80% to 100%.
[0040] By controlling the silicon content of the negative electrode within the aforementioned range, it is beneficial to better control the expansion and contraction changes of the negative electrode, reduce the generation of fresh interfaces, inhibit the negative electrode interface side reactions, reduce the consumption rate of the first additive, reduce the battery internal resistance growth rate, and maintain a better fast charging performance for a longer period of time. For example, among silicon-based materials, the volume expansion and contraction changes of silicon-carbon composite materials are relatively low.
[0041] In some embodiments, the electrolyte satisfies one or more of the following characteristics:
[0042] (e1) the mass percentage of the first additive in the electrolyte is 0.01% to 3.2%;
[0043] (e2) The mass ratio of the second additive to the first additive is 0.01 to 50.
[0044] In some embodiments, the electrolyte satisfies one or more of the following characteristics:
[0045] (e1') the mass percentage of the first additive in the electrolyte is 0.05% to 1.6%;
[0046] (e2′) The mass ratio of the second additive to the first additive is 0.1 to 30.
[0047] By controlling the mass percentage of the first additive in the electrolyte within the aforementioned range, the first additive can continue to play a role in repairing the SEI film during fast charging and cycling, and can maintain better fast charging performance for a longer period of time.
[0048] By controlling the mass ratio of the second additive to the first additive within the aforementioned range, the first additive and the second additive can better exert a synergistic effect, which is beneficial for improving the negative electrode SEI film and inhibiting fast charging gas production while better inhibiting the increase in negative electrode interface impedance, thereby better improving the fast charging performance of lithium-ion secondary batteries.
[0049] By controlling the mass percentage of the first additive in the electrolyte and the mass ratio of the second additive to the first additive within the aforementioned range, it is beneficial to better exert the synergistic effect between the first additive and the second additive and better improve the fast charging performance of the lithium-ion secondary battery.
[0050] In some embodiments, the second additive includes one or more of a lithium salt additive, a phosphate ester additive, vinylene carbonate, a fluorocarbonate additive, a saturated sultone, and a cyclic sulfate;
[0051] In some embodiments, the electrolyte satisfies one or more of the following characteristics:
[0052] (f1) The lithium salt additive includes one or more of oxalate lithium salt, lithium tetrafluoroborate, lithium difluorophosphate and fluorosulfonic acid lithium salt; the oxalate lithium salt includes one or more of lithium difluorooxalatoborate, lithium difluorobisoxalatophosphate and lithium tetrafluorooxalatophosphate; the fluorosulfonic acid lithium salt includes one or more of lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide;
[0053] (f2) the phosphate additive includes a silicon-based phosphate additive; the silicon-based phosphate additive includes one or more of tris(trimethylsilyl)phosphate (TMSP) and tris(trimethylsilyl)phosphite (TMSPi);
[0054] (f3) The fluorocarbonate additive includes fluoroethylene carbonate;
[0055] (f4) The cyclic sulfate ester includes one or more of monocyclic sulfate ester and polycyclic sulfate ester.
[0056] In some embodiments, the electrolyte satisfies one or more of the following characteristics:
[0057] (g1) the mass percentage of the lithium salt additive in the electrolyte is 0-3%;
[0058] (g2) the lithium salt additive includes lithium difluorooxalate borate, and the mass percentage of lithium difluorooxalate borate in the electrolyte is 0-3%;
[0059] (g3) The lithium salt additive includes lithium bis(fluorosulfonyl)imide;
[0060] (g4) The mass percentage of the phosphate additive in the electrolyte is 0-2%;
[0061] (g5) the mass percentage of the vinylene carbonate in the electrolyte is 0-3%;
[0062] (g6) the mass percentage of the fluorocarbonate additive in the electrolyte is 0-10%;
[0063] (g7) the fluorinated carbonate additive includes fluoroethylene carbonate, and the mass percentage of fluoroethylene carbonate in the electrolyte is 0-10%, and can be optionally 0-5%;
[0064] (g8) the mass percentage of the saturated sultone in the electrolyte is 0-3%;
[0065] (g9) the mass percentage of the cyclic sulfate in the electrolyte is 0-3%;
[0066] (g10) The cyclic sulfate ester includes a polycyclic sulfate ester, and the mass percentage of the polycyclic sulfate ester in the electrolyte is 0-3%.
[0067] By selecting the second additive to have the aforementioned type and / or amount, it is beneficial to better exert the competitive effect and synergistic effect between the first additive and the second additive, and better improve the battery performance.
[0068] For example, the negative electrode film-forming impedance of lithium salt additives and phosphate additives is low. By introducing one or more of lithium salt additives and phosphate additives into the electrolyte, it is beneficial to reduce the interfacial impedance of the negative electrode SEI film and improve the fast charging performance of lithium-ion secondary batteries.
[0069] For example, vinylene carbonate (VC) can optimize the SEI film. By introducing VC into the electrolyte, it is beneficial to reduce or delay the negative electrode film consumption of the first additive, and better control the charge transfer impedance on the negative electrode surface and the battery internal resistance.
[0070] For example, fluorocarbonate additives (such as fluoroethylene carbonate (FEC)) can form a relatively strong interface film with lower ion transfer impedance on the surface of the negative electrode at room temperature. By introducing fluorocarbonate additives (such as FEC) into the electrolyte, it is beneficial to reduce or delay the consumption of the first additive in the negative electrode film formation, and better control the negative electrode interface impedance and battery internal resistance.
[0071] For example, saturated sultones (such as 1,3-propane sultone (PS) etc.) can participate in the negative electrode film formation to form a dense and stable negative electrode SEI film, which is beneficial to reduce or delay the negative electrode film formation consumption of the first additive and better control the negative electrode interface impedance and battery internal resistance.
[0072] For example, by introducing cyclic sulfate into the electrolyte, the negative electrode interface film can be optimized, the stability of the negative electrode SEI film can be improved, the negative electrode interface side reactions can be reduced and gas production can be inhibited during fast charging, and the negative electrode interface impedance and battery internal resistance can be better controlled.
[0073] In some embodiments, the electrolyte includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and the molar volume concentration of the lithium bis(fluorosulfonyl)imide in the electrolyte is 0.01 mol / L to 0.5 mol / L.
[0074] Lithium bis(fluorosulfonyl)imide (LiFSI) can participate in the formation of a stable solid electrolyte interface film at the positive and negative electrodes. On the one hand, by introducing LiFSI into the electrolyte, the stability of the positive and negative electrode interface films can be improved, and the electrolyte interface side reactions at the positive and negative electrodes can be reduced and gas production can be suppressed during fast charging. On the other hand, LiFSI has a better ability to dissociate lithium ions than lithium hexafluorophosphate (LiPF6), so the addition of LiFSI is also beneficial to improve the liquid phase conductivity. Therefore, by introducing LiFSI into the electrolyte, the fast charging performance of lithium-ion secondary batteries can be better improved.
[0075] In some embodiments, the electrolyte satisfies one or more of the following characteristics:
[0076] (h1) the molecular weight of the first additive is less than or equal to 500 Da;
[0077] (h2) the molecule of the first additive contains 1 to 4 carbon-carbon triple bonds;
[0078] (h3) the carbon-carbon triple bond in the first additive is CH≡C-;
[0079] (h4) The first additive includes one or more of a first alkynyl compound and a second alkynyl compound; wherein the first alkynyl compound contains a carbon-carbon triple bond and a Lewis base nitrogen heterocycle, the carbon-carbon triple bond and the Lewis base nitrogen heterocycle in the first alkynyl compound are connected by a linker L1, and the linker L1 contains a C covalently bonded to the carbon-carbon triple bond. 1-3 The second alkynyl compound contains a carbon-carbon triple bond and an alkyl carbonate group, the structure of the alkyl carbonate group is R2-OC(=O)-O-*, where * is a bonding site connected to a carbon atom, and R2 is C 1-3 The carbon-carbon triple bond in the second alkynyl compound and the alkyl carbonate group are connected by a linker L2, wherein the linker L2 contains a C covalently bonded to the carbon-carbon triple bond. 1-3 Alkylene.
[0080] In some embodiments, the electrolyte satisfies one or more of the following characteristics:
[0081] (i1) the molecular weight of the first additive is less than or equal to 300 Da;
[0082] (i2) the first additive contains 1 to 4 Lewis base nitrogen heterocycles in its molecule;
[0083] (i3) The Lewis base nitrogen heterocycle includes a substituted or unsubstituted imidazole group, wherein the imidazole ring in the substituted or unsubstituted imidazole group is substituted by 0, 1 or more substituent groups Q2, and the substituent groups Q2 in the substituted imidazole group are each independently C 1-3 an alkyl group, a cyano group or a fluorine atom;
[0084] (i4) The first alkynyl compound is composed of a carbon-carbon triple bond, a C 1-3 Alkylene and -OC(=O)-R 10 Composition, R 10 is a Lewis base nitrogen heterocycle; the second alkynyl compound is composed of a carbon-carbon triple bond, C 1-3 Alkylene and -OC(=O)-OR 20 Composition, R 20 C 1-3 alkyl.
[0085] In some embodiments, the first additive includes one or more of Compound II and Compound III;
[0086] The structure of compound II is Among them, L 11 C 1-3 Alkylene, Q2 is independently C 1-3 Alkyl, cyano or fluorine atom, p2 is 0, 1, 2 or 3;
[0087] The structure of the compound III is Among them, L 21 C 1-3 Alkylene, R 22 C 1-3 alkyl.
[0088] In some embodiments, the electrolyte satisfies one or more of the following characteristics:
[0089] (j1) the first additive includes compound II, and the mass proportion of compound II in the first additive is 80% to 100%;
[0090] (j2) The first additive includes a structure of The mass proportion of compound IIa in the first additive is 80% to 100%.
[0091] By controlling the molecular weight of the first additive within the aforementioned lower range, the first additive can have a smaller molecular size, which is beneficial for better controlling the low viscosity characteristics of the electrolyte, making the electrolyte have a higher conductivity, and can better cooperate with the solvent of formula I to improve the battery dynamics.
[0092] By controlling the number of carbon-carbon triple bonds in the first additive within the aforementioned range, the first additive can better cooperate with the solvent of formula I to improve the fast charging performance of the lithium-ion secondary battery, and it is also beneficial to inhibit the increase in interfacial impedance caused by the first additive participating in the formation and repair of the SEI film, and it is also beneficial to control the influence of the first additive on the liquid phase impedance; thereby, the battery dynamics can be better improved, and the fast charging performance of the lithium-ion secondary battery can be better improved.
[0093] The first alkynyl compound includes both a carbon-carbon triple bond and a Lewis base nitrogen heterocycle, which can promote the formation of an organic / inorganic dual-property interface film in the process of participating in the negative electrode interface reaction, improve the stability of the negative electrode SEI film, and can better cooperate with the solvent of formula I to comprehensively improve the fast charging performance of lithium-ion secondary batteries; the Lewis base nitrogen heterocycle can also absorb acid by-products in the electrolyte, which is beneficial to improving the stability of the negative electrode interface and the negative electrode active material, reducing the consumption rate of the first additive, reducing the battery internal resistance growth rate, and maintaining a better fast charging performance for a longer period of time.
[0094] By controlling the amount of the Lewis base nitrogen heterocycle in the first additive within the aforementioned range, it is beneficial to better absorb the acid byproducts in the electrolyte, and it is also beneficial to control the steric effect of the Lewis base nitrogen heterocycle on the carbon-carbon triple bond.
[0095] Examples of Lewis base nitrogen heterocycles include the imidazole ring in compound II and compound IIa.
[0096] In some embodiments, the electrolyte satisfies one or more of the following characteristics:
[0097] (k1) the mass proportion of the solvent of formula I in the chain carboxylic acid ester compound is 75% to 100%;
[0098] (k2) the mass proportion of the chain carboxylic acid ester compound in the non-aqueous solvent is 5% to 80%;
[0099] (k3) The conductivity of the electrolyte at 25° C. is 9 mS / cm to 25 mS / cm.
[0100] In some embodiments, the electrolyte satisfies one or more of the following characteristics:
[0101] (k1') the mass proportion of the solvent of formula I in the chain carboxylic acid ester compound is 90% to 100%;
[0102] (k2') the mass proportion of the chain carboxylic acid ester compound in the non-aqueous solvent is 10% to 60%;
[0103] (k3') The conductivity of the electrolyte at 25° C. is 10 mS / cm to 18 mS / cm.
[0104] By controlling the mass proportion of the solvent of formula I in the chain carboxylic acid ester compound, the mass proportion of the chain carboxylic acid ester compound in the non-aqueous solvent, and one or more parameters of the conductivity of the electrolyte at 25°C within the aforementioned range, it is beneficial to better improve the battery dynamics, thereby helping to give the lithium-ion secondary battery better fast charging performance. Among them, the chain carboxylic acid ester compound such as (solvent of formula I) has a relatively low viscosity, which is beneficial to improve the conductivity of the electrolyte.
[0105] In some embodiments of the second aspect of the present application, a method for preparing a lithium ion secondary battery is provided, comprising the following steps:
[0106] Placing an electrode assembly including a positive electrode sheet, a separator and a negative electrode sheet in a battery housing; wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet;
[0107] An electrolyte is injected into the battery housing, and the electrolyte is allowed to stand to infiltrate the positive electrode sheet and the negative electrode sheet to form an electrolyte; wherein the electrolyte comprises an electrolyte salt, a non-aqueous solvent and an additive; the non-aqueous solvent comprises a chain carboxylic acid ester compound, the chain carboxylic acid ester compound comprises a solvent of formula I, and the structure of the solvent of formula I is shown in formula (I): In formula (I), R 11 and R 12 Each independently is a methyl group or an ethyl group; the first additive and the second additive, the first additive is a non-ionic organic additive containing a carbon-carbon triple bond, and the second additive is a negative electrode film-forming additive different from the first additive.
[0108] The prepared lithium ion secondary battery has the advantages of the lithium ion secondary battery described in the first aspect of the present application.
[0109] In some embodiments, in the step of injecting electrolyte into the battery housing, the initial mass percentage of the first additive in the electrolyte is 0.1% to 5%.
[0110] In some embodiments, in the step of injecting electrolyte into the battery housing, the initial mass percentage of the first additive in the electrolyte is 0.1% to 3%.
[0111] In some embodiments, the lithium ion secondary battery described in the first aspect of the present application is prepared.
[0112] In some embodiments of the third aspect of the present application, an electrical device is provided, comprising at least one of the lithium ion secondary battery described in the first aspect of the present application and the lithium ion secondary battery prepared by the preparation method of the lithium ion secondary battery described in the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0113] The details of one or more implementations or embodiments of the present application are set forth in the following drawings and description. Other features, objects and advantages of the present application will become apparent from the description, drawings and claims.
[0114] In order to better describe and illustrate the embodiments, examples or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments, examples or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0115] Figure 1 It is a schematic diagram of a battery cell according to an embodiment of the present application.
[0116] Figure 2 for Figure 1 An exploded view of a battery cell according to an embodiment of the present application is shown.
[0117] Figure 3 FIG. 1 is a schematic diagram of a battery device according to an embodiment of the present application.
[0118] Figure 4 A schematic diagram of a battery pack according to an embodiment of the present application.
[0119] Figure 5 for Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0120] Figure 6 A schematic diagram of an electrical device using a lithium-ion secondary battery according to an embodiment of the present application as a power source.
[0121] Description of reference numerals:
[0122] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery device; 5. Battery cell; 51. Battery casing; 52. Electrode assembly; 53. Cover plate; 6. Electrical device. DETAILED DESCRIPTION
[0123] Below, some embodiments and examples of the lithium-ion secondary battery, preparation method and electrical device of the present application are described in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0124] "Scope" disclosed in the present application can be limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or excluding end values, and any end value can be included or not included independently, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are also listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation for these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to listing the parameter as, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.
[0125] In the present application, "numerical value" is involved, and its meaning includes the present number and its reasonable approximation. The definition of "numerical value" can be applied to discrete numerical points and the endpoints of the numerical range. If not specifically limited, "approximation" is involved, covering the numerical interval based on the reasonable fluctuation range of the present number, and the reasonable fluctuation range may vary due to the type and numerical size of the present number. The reasonable fluctuation range can be reasonably confirmed according to the accuracy of the test or measurement method. Therefore, when it comes to numerical values or numerical ranges, if there is no special explanation, it should be understood that the numerical value covers its reasonable approximation, and the numerical range covers the reasonable approximation of the two endpoints. Those skilled in the art can understand that the acceptable fluctuation range of the relevant approximation can be included in the definition of the numerical value or the numerical range. In the present application, if there is no other explanation, "N1" can be reasonably understood as "about N1", and "N1~N2" can be reasonably understood as "about N1 to about N2", wherein N1 and N2 are two unequal numerical values.
[0126] In this application, unless otherwise specified, "about" means within a reasonable range above and below the number, and the fluctuation range may vary depending on the type and value of the number. For example, it may be allowed to be within a range of ±10%, ±5%, ±2%, ±1%, etc. For example, taking "about 20°C" and its approximate value of ±1°C as an example, the approximate values of 19°C, 19.5°C, etc. within the approximate range shown in "about 20°C" should also be included in the range indicated by "about 20°C".
[0127] In this application, when "multiple", "multiple", "multiple" and the like are involved, unless otherwise specified, they refer to a number greater than or equal to 2. For example, "one or more" means one or ≥ (greater than or equal to) two. It is understood that when "any number" of items are involved, it refers to any suitable combination of multiple items, that is, the combination of "any number" of items is performed in a manner that does not conflict and can implement this application.
[0128] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0129] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.
[0130] Those skilled in the art will appreciate that in the methods of the various embodiments or embodiments of the present application, if not particularly limited, the order of writing of each step does not mean a strict execution order and constitutes any limitation to the implementation process, and the detailed execution order of each step should be determined by its function and possible internal logic. If there is no special description, all steps of the present application can be performed in sequence, or can be performed randomly, and can preferably be performed in sequence. For example, method M includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed in sequence, or steps (b) and (a) performed in sequence. For example, method M may also include step (c), indicating that step (c) can be added to method M in any order, for example, method M may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.
[0131] In the present application, in the open technical features or technical solutions described by the words "contain", "include", "include", etc., if there is no other explanation, additional members other than the listed members are not excluded, and it can be regarded as providing both closed features or solutions consisting of the listed members and open features or solutions including additional members in addition to the listed members. For example, a includes a1, a2 and a3. If there is no other explanation, it may also include other members or may not include additional members. It can be regarded as providing both the feature or solution of "a consists of a1, a2 and a3" or "a is selected from a1, a2 and a3", and the feature or solution of "a includes not only a1, a2 and a3, but also other members".
[0132] In the present application, unless otherwise specified, M (such as m1) means that m1 is a non-limiting example of M, and it can be understood that M is not limited to m1.
[0133] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel solutions of "yes" or "no". If there are multiple "optional" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent. Unless otherwise specified, the descriptions of "optionally include", "optionally include", etc. in this application, taking "optionally include" as an example, mean "may include or not include".
[0134] In the present application, unless otherwise specified, the features or solutions corresponding to "and / or" include any one of two or more related listed items, and also include any and all combinations of the related listed items, wherein any and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "M and / or N" means a group consisting of M, N, and "a combination of M and N". Among them, "including M and / or N" can mean "including M, including N, and including M and N", and can also mean "including M, including N, or including M and N", which can be properly understood according to the sentence in which it is located.
[0135] Herein, the word “suitable” in “suitable combination”, “suitable method”, etc., shall be based on the technical solution that can implement the present application.
[0136] Herein, "preferred", "better", "good", etc. are only used to describe implementation methods or examples with better effects, and it should be understood that they do not constitute a limitation on the scope of protection of this application. If multiple "preferred" items appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "preferred" item is independent.
[0137] In the present application, “further”, “furthermore”, “particularly”, “for example”, “such as”, “example”, etc. are used for descriptive purposes to indicate differences in content, but should not be understood as limiting the scope of protection of the present application.
[0138] In the present application, the terms "first", "second", "third", etc. in "the first aspect", "the second aspect", "the third aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third" only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0139] In the description of the present application, it should be understood that the terms "thickness", "height", "up", "down", "bottom", "inside", "outside", etc., indicating the orientation or positional relationship are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.
[0140] In this application, unless otherwise clearly specified or limited, the terms "connected" and "connection" related to mechanical structures should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection. For ordinary technicians in this field, the meanings of the above terms in this application can be understood according to the circumstances.
[0141] In the present application, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. In the present application, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean a relative positional relationship in terms of horizontal height, or may mean that there is an attachment relationship without limiting the relative positional relationship in terms of horizontal height.
[0142] In this application, the term "room temperature" or "normal temperature" generally refers to 4°C to 35°C, and may refer to 20°C ± 5°C. In some embodiments or examples of this application, room temperature refers to 20°C to 30°C. In some embodiments or examples of this application, "normal temperature" is 20°C to 35°C, and may be 20°C to 30°C.
[0143] In this application, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left endpoint and the right endpoint are the same. For example, 3~5 μm or 3-5 μm both mean that the units of the left endpoint "3" and the right endpoint "5" are both μm (micrometers), which have the same meaning as 3 μm ~5 μm. In addition, similar descriptions of other parameters such as temperature and size are also understood in the same way.
[0144] In this application, unless otherwise specified, the term "molecular weight" refers to the molecular weight measured in Daltons (Da), where 1 Dalton is equal to 12 One twelfth of the atomic mass of C.
[0145] In this application, "greater than or equal to", "greater than or equal to" and "≥" have the same meaning and can be used interchangeably; "less than or equal to", "less than or equal to" and "≤" have the same meaning and can be used interchangeably; "greater than" can be equivalently expressed as ">", and "less than" can be equivalently expressed as "<". In this application, unless otherwise specified, "greater than or equal to" and "≥" can be regarded as providing two solutions of "greater than" and "equal to". In this application, unless otherwise specified, "less than or equal to" and "≤" can be regarded as providing two solutions of "less than" and "equal to".
[0146] In the present application, exemplary descriptions such as "in some implementation modes (or examples)" and "in one implementation mode (or example)" may include but are not limited to the following meanings: these solutions may be combined with other solutions in a suitable manner to form a new technical solution.
[0147] The improved effects described in this application, unless otherwise stated, are not intended to be limited to any theory.
[0148] For traditional lithium-ion secondary batteries, during the fast charging process, the electrolyte is prone to decomposition reaction and gas production. During the fast charging process, as the temperature inside the battery rises, the reaction rate accelerates, and the interface side reaction and gas production problems are likely to become more serious. The gas production problem accompanied by the interface side reaction will deteriorate the cycle performance of the fast charging battery.
[0149] According to various implementations and examples of the present application, the present application provides a lithium ion secondary battery, a preparation method and an electric device. The lithium ion secondary battery has improved fast charging performance.
[0150] In this application, unless otherwise specified, the term "lithium-ion secondary battery" refers to a secondary battery whose active ions include lithium ions, and "lithium-ion battery cell" refers to a battery cell whose active ions include lithium ions. Typically, a lithium-ion secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. A separator is provided between the positive electrode sheet and the negative electrode sheet. The separator mainly plays the role of preventing the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0151] In the present application, unless otherwise specified, the "electrode active material layer" includes at least one of the positive electrode active material layer of the positive electrode sheet and the negative electrode active material layer of the negative electrode sheet. Depending on the detailed circumstances, the electrode active material layer may refer to the positive electrode active material layer or the negative electrode active material layer. It can be understood that the positive electrode active material layer contains positive electrode active materials, and the negative electrode active material layer contains negative electrode active materials. In the present application, the "electrode active material layer" may also be recorded as the "active material layer", the "positive electrode active material layer" may also be recorded as the "positive electrode active layer", and the "negative electrode active material layer" may also be recorded as the "negative electrode active layer".
[0152] In this application, the terms "electrode plate" and "electrode plate" have the same meaning and can be used interchangeably. The electrode plate can be a positive electrode plate or a negative electrode plate, and the "active material" or "active substance" in the electrode plate has the ability to reversibly embed and extract active ions.
[0153] In the present application, the term "negative electrode sheet" includes a negative electrode active layer, and the negative electrode active layer includes a negative electrode active material. The term "negative electrode active material" refers to a material used in a negative electrode sheet that can reversibly insert and extract active ions.
[0154] In this application, unless otherwise specified, "negative electrode sheet" includes a negative electrode current collector. "Negative electrode current collector" refers to a structure responsible for collecting and conducting electrons at the negative electrode. In the negative electrode sheet, the negative electrode active layer is located on at least one side of the negative electrode current collector, and can be located on one side or both sides of the negative electrode current collector.
[0155] In the present application, the term "positive electrode sheet" includes a positive electrode active layer, and the positive electrode active layer includes a positive electrode active material. The term "positive electrode active material" refers to a material used in a positive electrode sheet that can reversibly extract and insert active ions.
[0156] In this application, unless otherwise specified, "positive electrode sheet" includes positive electrode current collector. "Positive electrode current collector" refers to the structure responsible for collecting and conducting electrons at the positive electrode. In the positive electrode sheet, the positive electrode active layer is located on at least one side of the positive electrode current collector, and can be located on one side or both sides of the positive electrode current collector.
[0157] In the present application, unless otherwise specified, "separation membrane" and "diaphragm" have the same meaning and can be used interchangeably.
[0158] In a first aspect of the present application, a lithium ion secondary battery is provided, the lithium ion secondary battery having improved fast charging performance.
[0159] In some embodiments, the lithium ion secondary battery includes an electrolyte, the electrolyte includes an electrolyte salt, a non-aqueous solvent and an additive; the non-aqueous solvent includes a chain carboxylic acid ester compound, and the chain carboxylic acid ester compound includes a structure of R 11 -C(=O)-OR 12 The solvent of formula I, R 11 and R 12 Each independently is a methyl group or an ethyl group; the additive includes a first additive and a second additive, the first additive is a non-ionic organic additive containing a carbon-carbon triple bond, and the second additive is a negative electrode film-forming additive different from the first additive. The lithium-ion secondary battery has significantly improved fast charging performance.
[0160] In some embodiments, the lithium ion secondary battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein a separator is disposed between the positive electrode sheet and the negative electrode sheet; the electrolyte comprises an electrolyte salt, a non-aqueous solvent and an additive; the non-aqueous solvent comprises a chain carboxylate compound, and the chain carboxylate compound comprises a structural formula R 11 -C(=O)-OR 12 The solvent of formula I, R 11 and R 12 Each independently is a methyl group or an ethyl group; the additive includes a first additive and a second additive, the first additive is a non-ionic organic additive containing a carbon-carbon triple bond, and the second additive is a negative electrode film-forming additive different from the first additive. The lithium-ion secondary battery has excellent fast charging performance.
[0161] In some embodiments of the first aspect of the present application, a lithium ion secondary battery is provided, which includes a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein a separator is provided between the positive electrode sheet and the negative electrode sheet; the electrolyte includes an electrolyte salt, a non-aqueous solvent and an additive; the non-aqueous solvent includes a chain carboxylate compound, the chain carboxylate compound includes a solvent of formula I, and the structure of the solvent of formula I is shown in formula (I): In formula (I), R 11 and R 12 Each independently is a methyl group or an ethyl group; the additive includes a first additive and a second additive, the first additive is a non-ionic organic additive containing a carbon-carbon triple bond, and the second additive is a negative electrode film-forming additive different from the first additive.
[0162] In the present application, unless otherwise specified, "non-aqueous solvent" refers to a solvent that is not water.
[0163] In this application, unless otherwise specified, "chain carboxylic acid ester compounds" refer to chain compounds having a -C(=O)-O- structure. Chain carboxylic acid ester compounds used as non-aqueous solvents in electrolytes generally have lower viscosity, which is beneficial for providing higher conductivity. Among them, the viscosity of the "Formula I solvent" is lower and has higher conductivity.
[0164] In the present application, unless otherwise specified, a "carbon-carbon triple bond" is an unsaturated bond having a -C≡C- skeleton.
[0165] In this application, unless otherwise specified, "acetylene additives" are compounds containing a carbon-carbon triple bond (-C≡C-), and "first additives" are non-ionic acetylene organic additives, which are non-ionic organic additives containing a carbon-carbon triple bond. It is understood that salt additives are not within the scope of the first additive. The first additive can participate in the formation of the negative electrode solid electrolyte interface (SEI) film. The first additive can significantly improve the high temperature performance of the battery, including extending the high temperature cycle and storage life, and can be used as a high temperature additive. However, when the first additive is used as a single additive, it is easy to cause a large negative electrode interface impedance at room temperature.
[0166] In the present application, unless otherwise specified, the "second additive" is a negative electrode film-forming additive that is different from the first additive. "Negative electrode film-forming additive" refers to an additive that can decompose at the negative electrode working potential and participate in the formation of the negative electrode SEI film. The higher the reduction potential of the negative electrode film-forming additive, that is, the more positive the potential value relative to Li / Li⁺, the earlier the negative electrode film-forming additive decomposes, and then participates in the formation of the negative electrode SEI film. It is understandable that some negative electrode film-forming additives can also participate in the formation of an interfacial film (CEI film) at the positive electrode. Generally, those skilled in the art can judge whether a certain additive can participate in the formation of the negative electrode SEI film based on methods such as reduction potential analysis, decomposition product and SEI film composition analysis, and electrochemical performance verification; illustratively, the reduction potential of the additive can be measured by cyclic voltammetry in a simulated battery environment (such as lithium metal to the working electrode); illustratively, the SEI film composition can be analyzed by chemical composition analysis methods including but not limited to X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR), etc.; illustratively, whether a certain additive introduced can participate in the formation of the negative electrode SEI film can be judged based on the changes in performance indicators such as the first coulomb efficiency, cycle stability, and impedance spectrum when the additive is introduced or not.
[0167] In the lithium-ion secondary battery provided in the first aspect of the present application, it can be understood that the positive electrode plate and the negative electrode plate are soaked in the electrolyte.
[0168] The lithium-ion secondary battery introduces a non-ionic acetylene organic additive (referred to as the first additive) and a second additive (a negative electrode film-forming additive different from the first additive) when using a highly conductive solvent. 11 and R 12 All of them have a small number of carbon atoms, which makes the solvent of formula I have a lower viscosity and a higher conductivity; secondly, the first additive can participate in the formation and repair of the solid electrolyte interface (SEI) film at the negative electrode, which can significantly improve the stability of the SEI film, thereby significantly inhibiting the interfacial side reactions between the negative electrode and the electrolyte during the fast charging process, and the problem of the easy decomposition and gas production of the solvent of formula I is significantly inhibited; thirdly, the second additive can competitively participate in the negative electrode film formation, which can reduce or delay the negative electrode film formation consumption of the first additive, and can inhibit the increase in the negative electrode interface impedance caused by the participation of the first additive in the negative electrode film formation; based on the synergy of the aforementioned effects, but not limited to the aforementioned theory, the lithium-ion secondary battery has an improved fast charging performance and extends the cycle life of the fast charging battery system.
[0169] The types and concentrations of inorganic components in the electrolyte (including electrolyte salts and inorganic additives) can be tested with reference to relevant standards such as GB / T 34672-2017 General Rules for Ion Chromatography of Chemical Reagents and GB / T 6040-2019 General Rules for Infrared Spectroscopy Analysis, and updated versions of standard methods can be preferred. The types and contents of organic components in the electrolyte (including non-aqueous solvents and organic additives) can be tested with reference to relevant standards such as GB / T 9722-2023 General Rules for Gas Chromatography of Chemical Reagents.
[0170] In addition, those skilled in the art can also identify the components contained in the electrolyte of the lithium-ion secondary battery by one or more of the following detection methods, including but not limited to: nuclear magnetic resonance hydrogen spectroscopy ( 1 H NMR) method, high performance liquid chromatography (HPLC) method, matrix-assisted laser desorption-mass spectrometry (MADI-TOF) method, Fourier transform infrared spectroscopy (FT-IR) method, ultraviolet spectroscopy, gas chromatography (GC) method, etc. The sample preparation methods and test methods of these test methods are known to those skilled in the art, and the test parameters can be appropriately adjusted according to the structure of the material or substance and the sample characteristics. As a non-limiting example, FT-IR, ultraviolet spectroscopy, 1 The component types and contents of the electrolyte are detected by one or more methods such as H NMR, mass spectrometry, MADI-TOF, GC, etc., but are not limited thereto.
[0171] The sample of electrolyte to be tested can be obtained by disassembling the battery cell.
[0172] In some embodiments, the linear carboxylic acid ester compound includes one or more of methyl formate, ethyl formate, methyl acetate and ethyl acetate.
[0173] In some embodiments, the negative electrode plate includes a negative electrode active layer, the negative electrode active layer includes a negative electrode active material, and the average particle size of the primary particles in the negative electrode active material is recorded as D1, wherein D1 is 0.1μm~2μm, and can be optionally 0.5μm~1.2μm, and can be further optionally 0.5μm~1.0μm, and can also be any of the following values or a range selected from any two of the following values: 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.4μm, 1.5μm, 1.6μm, 1.8μm, 2μm, etc.
[0174] In this application, unless otherwise specified, the "average particle size of primary particles" or "average particle size of primary particles" in the negative electrode active material refers to the average particle size of each primary particle of the negative electrode active material. "Primary particle size" refers to the maximum diameter of the primary particles in each direction.
[0175] In the present application, unless otherwise specified, the "primary particles" in the negative electrode active material are the basic units of particles in the negative electrode active material. It is understood that there are primary particles in the negative electrode active material. In the negative electrode active material, the primary particles can be in a non-agglomerated state or can be formed into agglomerates by multiple primary particles. The non-agglomerated primary particles can be referred to as "non-agglomerated primary particles", and the agglomerates formed by multiple primary particles can be referred to as "secondary particles".
[0176] By controlling the average particle size of the primary particles in the negative electrode active material (denoted as D1) within the aforementioned range, it is possible to control the negative electrode active material to have a more suitable ion transmission path and achieve a better rate, and at the same time, better control the negative electrode interface reaction, control the negative electrode film consumption of the first additive, better optimize the SEI film and inhibit gas production. Based on the synergy of the aforementioned effects, but not limited to the aforementioned theory, it is beneficial to better control the internal resistance of the battery and to enable the lithium-ion secondary battery to achieve better fast charging performance.
[0177] The particle morphology of the negative electrode active material can be used to count the particle size and average value of the primary particles in the negative electrode active material. The particle morphology of the negative electrode active material can be obtained by using a scanning electron microscope (such as ZEISS Sigma 300, JEOL scanning electron microscope, Axia ChemiSEM scanning electron microscope, etc.). The sample to be tested can be obtained by laying and sticking the powder sample of the negative electrode active material on a conductive glue. In a non-limiting manner, the SEM test can refer to JY / T(001)-1996. Randomly select one or more areas in the sample to be tested for scanning testing, and based on the SEM image at a certain magnification, count the particle size of each primary particle in the scanned area and the frequency of occurrence of different particle sizes, and then calculate the average particle size of the primary particles counted. In a non-limiting manner, the magnification of a single scanning area can be 1000X, but is not limited thereto. In order to improve the accuracy of the statistical results, multiple areas can be randomly selected for scanning.
[0178] In some embodiments, the D of the negative electrode active material v 50 is 5μm~18μm, and can be optionally 6μm~15μm, and can further be 8μm~12.5μm. It can also be any of the following values or a range consisting of any two of the following values: 5μm, 5.5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm, etc.
[0179] In the context of this application, the volume cumulative distribution particle size D v N (where N represents any value selected from 0 to 100) is used to characterize the particle size of the material, which refers to the particle size corresponding to when the cumulative volume distribution percentage of the material reaches N%, and the particle size is less than or equal to D v The volume percentage of N is N%. v N can be obtained from the volume cumulative distribution curve of the material particle size. If there is no other explanation, the volume cumulative distribution curve starts from zero from the small particle size side. v 50 is used as an example. In this application, unless otherwise specified, D v 50 refers to the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%. This parameter indicates that the particle size of particles accounting for 50% of the volume of the material is less than or equal to D v 50, and 50% of the particles by volume are larger than D v 50. Those skilled in the art will appreciate that v 50. D v 10. D v 1, and can be measured by instruments and methods known in the art. For example, it can be conveniently measured by laser particle size analyzer with reference to GB / T 19077-2016 particle size distribution laser diffraction method, such as Mastersizer 2000E laser particle size analyzer and LS-909 laser particle size analyzer (OMEC) of Malvern Instruments Ltd., UK. Further, for equipment models such as Malvern 2000 (MasterSizer 2000) laser particle size analyzer, the standard process GB / T19077-2016 / ISO 13320:2009 can be referred to for testing.
[0180] By increasing the D v 50 is controlled within the aforementioned range, the specific surface area of the negative electrode active material can be controlled within a relatively low range, which is beneficial to reducing the negative electrode interface side reactions, reducing or delaying the negative electrode interface consumption of the first additive, optimizing the SEI film and inhibiting gas production during fast charging, and is also beneficial to better control the overall ion transmission path of the negative electrode active material particles. Based on the synergy of the aforementioned effects, but not limited to the aforementioned theory, it is beneficial to better control the battery internal resistance and to enable the lithium-ion secondary battery to achieve better fast charging performance.
[0181] By synergistically controlling the D v50 and the average particle size of the primary particles in the negative electrode active material, which is beneficial to take into account the ion transmission path of the primary particles and the particles as a whole in the negative electrode active material, and at the same time better inhibit the negative electrode interface side reaction and inhibit gas production. Based on the synergy of the above-mentioned effects, but not limited to the above-mentioned theory, it is beneficial to better control the internal resistance of the battery and to enable the lithium-ion secondary battery to achieve better fast charging performance.
[0182] In some embodiments, the D of the negative electrode active material v 50 is 5 μm to 18 μm, and the average particle size (D1) of the primary particles is 0.1 μm to 1.8 μm; optionally, the D v 50 is 0.4μm~1.1μm. D of negative electrode active material v 50 and D1 may also be further combined with the values or ranges in other embodiments. v 50 is controlled within the aforementioned range, and can be matched with a relatively small average primary particle size to shorten the lithium ion diffusion path.
[0183] In some embodiments, the following method can be used to test the D of the negative electrode active material or the positive electrode active material: v 50. D v 10. D v 1. Malvern 2000 (MasterSizer 2000) laser particle size analyzer was used, and the reference standard process was GB / T19077-2016 / ISO 13320:2009. The detailed test process included: taking an appropriate amount of the sample to be tested, adding a solvent (the solvent can be deionized water, and the sample concentration can be controlled at 8%~12% shading), ultrasonic treatment for 5 min (53KHz / 120W) to fully disperse the sample, and then measuring the sample according to GB / T19077-2016 / ISO 13320:2009 standard. Non-limiting examples of solvents include deionized water and anhydrous ethanol. After the sample is poured into the injection tower, it circulates with the solution to the test optical path system. When the particles are irradiated by the laser beam, the particle size distribution characteristics of the particles can be obtained by receiving and measuring the energy distribution of the scattered light. A particle size volume distribution diagram is drawn based on the test data, and D is obtained from the distribution diagram. v 50. D v 10. D v 1 and other parameters. In order to avoid the influence of agglomeration in the drying process on the particle size test, the washed wet sample was taken for dispersion test.
[0184] In some embodiments, the D of the negative electrode active material vThe ratio of 50 to D1 is 5~50, and can be 8~30, and can be further 10~20. It can also be any of the following values or a range consisting of any two of the following values: 5, 6, 8, 10, 15, 20, 25, 30, 35, 40, 45, 50, etc.
[0185] In some embodiments, the negative electrode active material includes a coated negative electrode material, and the coated negative electrode material includes a negative electrode active body and a carbon coating layer located at least in part of the negative electrode active body. It is understood that the carbon coating layer in the coated negative electrode material is different from the chemical composition of the negative electrode active body. The negative electrode active body can select at least one material suitable for negative electrode active materials known in the art. Without limitation, the negative electrode active body can include one or more of graphite and silicon-based materials. Without limitation, graphite can include one or more of natural graphite and artificial graphite. Without limitation, the silicon-based material can include one or more of elemental silicon, silicon oxide, silicon-carbon composite material, silicon-nitrogen composite material and silicon alloy. Without limitation, the carbon coating layer in the coated negative electrode material can include one or more of soft carbon, hard carbon and amorphous carbon. Without limitation, the average thickness of the carbon coating in the coated negative electrode material can be 1nm~500nm, optionally 100nm~500nm, and further optionally 100nm~200nm. In a non-limiting manner, the mass percentage of the coating layer in the coated active material is 0.2% to 5%, and may be 0.5% to 3%.
[0186] "Soft carbon" and "hard carbon" have well-known meanings in the art. Soft carbon can be graphitized after further high-temperature treatment, while hard carbon is difficult to graphitize even after further high-temperature treatment. In this application, unless otherwise specified, "amorphous carbon" refers to a transitional carbon material with a very low degree of graphitization crystallization and a nearly amorphous form (or without a fixed shape and periodic structural regularity).
[0187] In some embodiments, the carbon coating layer in the coated negative electrode material is one of a soft carbon coating layer, a hard carbon coating layer and an amorphous carbon coating layer. It can be understood that the material composition of the soft carbon coating layer is mainly soft carbon, the material composition of the hard carbon coating layer is mainly hard carbon, and the material composition of the amorphous carbon coating layer is mainly amorphous carbon.
[0188] In some embodiments, the negative electrode active material includes a coated negative electrode material, and the average particle size D1 of the primary particles of the negative electrode active material is 0.1μm~1.6μm, which can be optionally 0.4μm~1.0μm, or any of the following values or a range consisting of any two of the following values: 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.4μm, 1.5μm, 1.6μm, etc.
[0189] In some embodiments, the negative electrode plate satisfies one or more of the following characteristics:
[0190] (a1) The mass proportion of the coated negative electrode material in the negative electrode active material is 80% to 100%, and can be 90% to 100%, or any of the following percentages or a range consisting of any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.;
[0191] (a2) The coated negative electrode material includes coated graphite, and the negative electrode active body in the coated graphite includes a graphite body; without limitation, the mass proportion of the coated graphite in the negative electrode active material is 80% to 100%, and can be 90% to 100%, and can also be any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.
[0192] In the present application, "coated graphite" is a coated negative electrode material, in which the negative electrode active body includes a graphite body; the coated graphite includes a graphite body and a carbon coating layer located on at least a portion of the surface of the graphite body.
[0193] In the present application, a "graphite body" consists of graphite.
[0194] By providing a coated negative electrode material (such as coated graphite) including a carbon coating layer in the negative electrode active material, the lithium ion transmission channel on the surface of the negative electrode active material can be optimized, lithium ion transmission can be promoted, and the dynamics of the lithium ion secondary battery can be improved. At the same time, it is also beneficial to inhibit the negative electrode interface side reactions and inhibit the increase in interface impedance caused by the participation of the first additive in film formation, which is beneficial to better improve the fast charging performance of the lithium ion secondary battery.
[0195] By providing a coated negative electrode material including a carbon coating layer (such as coated graphite) in the negative electrode active material, the rate performance can be optimized by combining a relatively small average primary particle size.
[0196] In some embodiments, the coated negative electrode material is coated graphite.
[0197] In some embodiments, the positive electrode sheet includes a positive electrode active layer, and the positive electrode active layer includes a positive electrode active material; the positive electrode active material includes one or more of a lithium-containing phosphate positive electrode material and a lithium transition metal oxide positive electrode material;
[0198] In some embodiments, the positive electrode active material includes a lithium phosphate positive electrode material. In a non-limiting manner, the mass proportion of the lithium phosphate positive electrode material in the positive electrode active material is 80% to 100%, optionally 90% to 100%, further optionally 95% to 100%, and can also be any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.
[0199] In some embodiments, the positive electrode active material includes a lithium transition metal oxide positive electrode material. In a non-limiting manner, the mass proportion of the lithium transition metal oxide positive electrode material in the positive electrode active material is 80% to 100%, optionally 90% to 100%, further optionally 95% to 100%, and can also be any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.
[0200] In some embodiments, the positive electrode sheet satisfies one or more of the following characteristics:
[0201] (b1) The positive electrode active material includes a lithium-containing phosphate positive electrode material, and the D of the lithium-containing phosphate positive electrode material v 50 is 0.3 μm to 2 μm, and can also be any of the following values or a range consisting of any two of the following values: 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.8 μm, 2 μm, etc.;
[0202] (b2) The positive electrode active material includes a lithium transition metal oxide positive electrode material, and the D v 50 is 2μm~10μm, and can also be any of the following values or a range consisting of any two of the following values: 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc.
[0203] By controlling the type of positive electrode active material and the aforementioned D v 50, which is conducive to better coordination between the lithium ion extraction kinetics of the positive electrode and the lithium insertion kinetics of the negative electrode, which is conducive to reducing the internal resistance of the battery and better improving the fast charging performance.
[0204] In this application, unless otherwise specified, "lithium-containing phosphate positive electrode material" refers to a type of positive electrode active material containing iron-lithium phosphate components, and further refers to a positive electrode active material containing lithium elements, transition metal elements and phosphate ions (PO4 3- ) positive electrode active material. Unless otherwise specified, the "lithium-containing phosphate positive electrode material" may be an olivine structure.
[0205] In some embodiments, the positive electrode active material includes an olivine structured lithium phosphate-based positive electrode material. Non-limiting examples of olivine structured lithium phosphate-based positive electrode materials may include, but are not limited to, one or more of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. An example of lithium iron phosphate is LiFePO4. An example of lithium manganese phosphate is LiMnPO4.
[0206] A non-limiting example of the lithium-containing phosphate-based positive electrode material is a lithium iron phosphate-based positive electrode material.
[0207] In this application, unless otherwise specified, "iron lithium phosphate positive electrode material" refers to a type of positive electrode active material containing iron lithium phosphate components. Unless otherwise specified, the "iron lithium phosphate positive electrode material" may be an olivine structure.
[0208] In some embodiments, the positive electrode active material includes a lithium iron phosphate positive electrode material. Further, the lithium iron phosphate positive electrode material may include at least one of lithium iron phosphate and a composite material of lithium iron phosphate and carbon.
[0209] In some embodiments, the composite material of lithium iron phosphate and carbon is carbon-coated lithium iron phosphate.
[0210] In some embodiments, the lithium iron phosphate-based cathode material includes carbon-coated lithium iron phosphate.
[0211] In the present application, the term "carbon-coated lithium iron phosphate" includes a lithium iron phosphate body and a carbon coating layer located on at least a portion of the surface of the lithium iron phosphate body, and the lithium iron phosphate body contains lithium iron phosphate. Without limitation, the carbon coating layer in the carbon-coated lithium iron phosphate may include one or more of soft carbon, hard carbon and amorphous carbon. Without limitation, the mass proportion of the carbon coating layer in the lithium iron phosphate positive electrode material may be 1% to 1.5%.
[0212] In some embodiments, the lithium iron phosphate positive electrode material includes a lithium iron phosphate-based positive electrode material. The lithium iron phosphate-based positive electrode material refers to a type of positive electrode active material containing a lithium iron phosphate component.
[0213] In some embodiments, the lithium iron phosphate body includes lithium iron phosphate.
[0214] In some embodiments, the lithium iron phosphate-based positive electrode material includes carbon-coated lithium iron phosphate. In this case, the carbon-coated lithium iron phosphate includes carbon-coated lithium iron phosphate.
[0215] In the present application, the term "carbon-coated lithium iron phosphate" includes lithium iron phosphate and a carbon coating layer located at least on a portion of the surface of the lithium iron phosphate. Further, the carbon coating layer may include one or more of soft carbon, hard carbon and amorphous carbon.
[0216] In some embodiments, the carbon coating layer in the carbon-coated lithium iron phosphate includes soft carbon. In some embodiments, the carbon coating layer is a soft carbon coating layer, in which case the carbon-coated lithium iron phosphate can be recorded as soft carbon-coated lithium iron phosphate. "Soft carbon coating layer" refers to a coating layer mainly composed of soft carbon, and the mass proportion of soft carbon in the coating layer can be close to 100%. The mass proportion of soft carbon in the soft carbon coating layer in the carbon-coated lithium iron phosphate can be 1% to 1.5%, optionally 1.4% to 1.5%, but is not limited thereto.
[0217] In the present application, unless otherwise specified, "lithium transition metal oxide positive electrode material" refers to a positive electrode active material containing lithium, non-lithium metal elements and oxygen elements. Generally, the non-lithium metal elements in lithium transition metal oxide positive electrode materials include transition metal elements. Non-limitingly, in lithium transition metal oxide positive electrode materials, the molar percentage of transition metal elements relative to non-lithium metal elements can be 90% to 100%, and can also be any of the following percentages or a range selected from any two of the following percentages: 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.
[0218] In the present application, unless otherwise specified, “non-lithium metal element” refers to a metal element that is not lithium (Li) element.
[0219] In some embodiments, the lithium transition metal oxide positive electrode material includes a lithium nickel cobalt-based oxide positive electrode material. In the present application, the "lithium nickel cobalt-based oxide positive electrode material" includes lithium (Li) element, nickel (Ni) element, cobalt (Co) element and oxygen (O) element.
[0220] In some embodiments, the lithium nickel cobalt-based oxide positive electrode material may further include an M2 element, which may be a manganese (Mn) element or an aluminum (Al) element. When the M2 element is manganese (Mn), the lithium nickel cobalt-based oxide positive electrode material is a lithium nickel cobalt manganese-based oxide positive electrode material, which may be recorded as an NCM-based positive electrode material, and when the M2 element is aluminum (Al), the lithium nickel cobalt-based oxide positive electrode material is a lithium nickel cobalt aluminum-based oxide positive electrode material, which may be recorded as an NCA-based positive electrode material.
[0221] In some embodiments, the lithium composite metal oxide positive electrode material includes a ternary positive electrode material, which may be a ternary positive electrode material. In the present application, the "ternary positive electrode material" is composed of Li element, nickel element, cobalt element, M2 element and oxygen element; wherein the M2 element may be a manganese element or an aluminum element. When the M2 element is manganese (Mn), the ternary positive electrode material is lithium nickel cobalt manganese oxide, which may be recorded as NCM, and when the M2 element is aluminum (Al), the ternary positive electrode material is lithium nickel cobalt aluminum oxide, which may be recorded as NCA.
[0222] In some embodiments, the positive electrode active material includes a lithium transition metal oxide positive electrode material, and the D of the lithium transition metal oxide positive electrode material v 10 is greater than or equal to 1 μm.
[0223] In some embodiments, the positive electrode active material includes a lithium-containing phosphate positive electrode material, wherein the D v 10 is greater than or equal to 0.2 μm.
[0224] In some embodiments, the negative electrode plate includes a negative electrode active layer, which includes a negative electrode active material; the positive electrode plate includes a positive electrode active layer, which includes a positive electrode active material;
[0225] (c1) D of negative electrode active material v 1 greater than or equal to 1.5 μm;
[0226] (c2) The positive electrode active material includes a lithium transition metal oxide positive electrode material, and the D v 10 greater than or equal to 1 μm;
[0227] (c3) The positive electrode active material includes a lithium-containing phosphate positive electrode material, and D of the lithium-containing phosphate positive electrode material v 10 is greater than or equal to 0.2μm.
[0228] By controlling the D v 1. D of positive electrode active material v Controlling one or both of 10 within the aforementioned range is beneficial to reducing the content of smaller particles with extremely small size and extremely large specific surface area at the negative electrode and / or the positive electrode, which is beneficial to better inhibiting the interface side reactions of the negative electrode and / or the positive electrode, and better inhibiting fast charging and gas production.
[0229] By controlling the D v 1 Within the aforementioned range, the negative electrode interface side reaction can be significantly inhibited, the consumption rate of the first additive can be reduced, and the battery internal resistance growth rate can be reduced, which is conducive to maintaining a better fast charging performance for a longer period of time.
[0230] The first additive can adsorb transition metal ions in the electrolyte. v 10 Within the aforementioned range, it is beneficial to better control the dissolution of transition metal ions in the positive electrode, so that the first additive can participate more in the formation and repair of the negative electrode interface film, which is beneficial to maintain better fast charging performance for a longer period of time.
[0231] By controlling the D v 10 Within the aforementioned range, it is beneficial to better control the water content of the positive electrode active material, thereby helping to reduce acid byproducts (such as hydrofluoric acid), and further helping to improve the stability of the negative electrode interface and the negative electrode active material, helping to reduce the consumption rate of the first additive, reducing the battery internal resistance growth rate, and helping to maintain a better fast charging performance for a longer period of time.
[0232] In some embodiments, the D of the negative electrode active material v 50 is 5μm~18μm (optionally 6μm~15μm), the D v 1 is greater than or equal to 1.5 μm.
[0233] In some embodiments, the positive electrode active material includes a lithium-containing phosphate positive electrode material, wherein the D v 50 is 0.3μm~2μm, containing lithium phosphate cathode materials D v 10 is greater than or equal to 0.2 μm.
[0234] In some embodiments, the positive electrode active material includes a lithium transition metal oxide positive electrode material, and the D of the lithium transition metal oxide positive electrode material v 50 is 2μm~10μm, and the D v 10 is greater than or equal to 1 μm.
[0235] In the present application, the sample to be tested of the "negative electrode active material" in the negative electrode sheet of the lithium-ion secondary battery can be obtained by disassembling the battery, taking out the negative electrode sheet, extracting the negative electrode active material from the negative electrode active layer of the negative electrode sheet by solvent washing, ultrasonic dispersion, centrifugal separation, graded sedimentation, etc., and drying to obtain a powder sample. The obtained powder sample can be used for laser particle size analysis and testing, and can also be used for other tests.
[0236] In the present application, the sample to be tested of the "positive electrode active material" in the positive electrode sheet of the lithium-ion secondary battery can be obtained by disassembling the battery, taking out the positive electrode sheet, and extracting the positive electrode active material from the positive electrode active layer of the positive electrode sheet by solvent washing, ultrasonic dispersion, centrifugal separation, graded sedimentation, sintering and other methods, and drying to obtain a powder sample. The obtained powder sample can be used for laser particle size analysis and testing, and can also be used for other tests. In addition, the powder material extracted from the positive electrode active layer can also be sintered to remove the organic components, thereby obtaining a powder sample of the positive electrode active material.
[0237] Exemplarily, the preparation of the powder sample of the positive electrode active material can be carried out by the following method: disassembling the battery, taking out the positive electrode plate, soaking and cleaning it with a solvent such as dimethyl carbonate to remove the residual electrolyte; scraping the powder material of the positive electrode active layer, using a solvent (such as N-methylpyrrolidone (NMP) etc.) to fully soak the powder material extracted from the positive electrode active layer, so that organic components such as binders are dissolved in the solvent (the dissolution can also be promoted by ultrasonic dispersion etc.), washing, filtering, collecting the solid phase, and then using the density difference to centrifuge to separate the relatively low-density conductive agent from the suspension, collecting the centrifugal precipitate to obtain the positive electrode active material to be tested.
[0238] In some embodiments, the negative electrode plate includes a negative electrode active layer, and the negative electrode active layer includes a negative electrode active material; the negative electrode active material includes at least one of a carbon-based material and a silicon-based material.
[0239] In a non-limiting manner, the carbon-based material may include one or more of graphite, soft carbon and hard carbon. Graphite may include one or more of artificial graphite and natural graphite. In a non-limiting manner, the carbon-based material may include one or more of artificial graphite, natural graphite, soft carbon and hard carbon. In a non-limiting manner, the mass proportion of silicon-based materials in the negative electrode active material may be 0-40%, optionally 1%-40%, further optionally 1%-25%, or 0%-25%, or any of the following percentages or a range selected from any two of the following percentages: 0, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, 35%, 40%, etc.
[0240] In some embodiments, the negative electrode active material includes a graphite-based material.
[0241] In the present application, "graphite-based material" refers to a negative electrode active material containing a graphite body, and the graphite-based material includes at least a graphite body. Unless otherwise specified, the mass proportion of the graphite body in the graphite-based material can be 90% to 100%, and can also be any of the following percentages or a range consisting of any two of the following percentages: 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%. Without limitation, the graphite-based material may include one or more of a coated graphite-based material and uncoated graphite. The coated graphite-based material includes a graphite body and a coating layer located at least a portion of the surface of the graphite body. It can be understood that the coating layer is different from the material in the graphite body. The graphite-based material may include one or more of artificial graphite and natural graphite. In some embodiments, the carbon-based material is a graphite-based material. In some embodiments, the negative electrode active material is a graphite-based material.
[0242] In some embodiments, the mass proportion of graphite-based materials in the negative electrode active material is 60%~100%, optionally 70%~100%, further optionally 75%~100%, further optionally 80%~100%, further optionally 90%~100%, further optionally 95%~100%, further optionally 97%~100%, and can also be any of the following percentages or a range consisting of any two of the following percentages: 60%, 65%, 70%, 75%, 80%, 85%, 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.
[0243] In some embodiments, the negative electrode active material includes a carbon-based material. In a non-limiting manner, the mass proportion of the carbon-based material in the negative electrode active material is 60% to 100%, optionally 60% to 99%, further optionally 75% to 99%, and can also be 70% to 100%, further can be 75% to 100%, further can be 80% to 100%, further can be 90% to 100%, further can be 95% to 100%, further can be 97% to 100%, and can also be any of the following percentages or a range selected from any two of the following percentages: 60%, 65%, 70%, 75%, 80%, 85%, 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.
[0244] In a non-limiting manner, the mass proportion of the silicon-based material in the negative electrode active material can be 0-40%, further optionally 0-30%, further optionally 0-25%, further optionally 0-20%, further optionally 0-10%, further optionally 0-5%, further optionally 0-3%, and can also be any of the following percentages or a range consisting of any two of the following percentages: 0, 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0. 14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3%, 4%, 5%, 6%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, etc.
[0245] In some embodiments, the negative electrode active material includes a silicon-based material. In a non-limiting manner, the mass proportion of the silicon-based material in the negative electrode active material can be 1% to 40%, optionally 1% to 25%, further optionally 1% to 10%, further optionally 1% to 5%, and can also be any of the following percentages or a range selected from any two of the following percentages: 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, 35%, 40%, etc.
[0246] In some embodiments, the negative electrode plate satisfies one or more of the following characteristics:
[0247] (d1) the mass proportion of the silicon-based material in the negative electrode active material is 0-40%, and can be 0-25% (also refer to the appropriate numerical value or range in any embodiment above and below);
[0248] (d2) The silicon-based material includes a silicon-carbon composite material, which includes a porous carbon matrix and elemental silicon located in the pores of the porous carbon matrix; without limitation, the mass proportion of the silicon-carbon composite material in the silicon-based material can be 80% to 100%, optionally 90% to 100%, or any of the following percentages or a range consisting of any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.
[0249] "Silicon-carbon composite material" is a silicon-based material, which includes a porous carbon matrix and elemental silicon located in the pores of the porous carbon matrix. The silicon-carbon composite material can be obtained by a vapor deposition method. Those skilled in the art can prepare the silicon-carbon composite material by conventional methods in the art.
[0250] By controlling the silicon content of the negative electrode within the aforementioned range, it is beneficial to better control the expansion and contraction changes of the negative electrode, reduce the generation of fresh interfaces, inhibit the negative electrode interface side reactions, reduce the consumption rate of the first additive, reduce the battery internal resistance growth rate, and maintain a better fast charging performance for a longer period of time. For example, among silicon-based materials, the volume expansion and contraction changes of silicon-carbon composite materials are relatively low.
[0251] In some embodiments, the positive electrode active material includes a positive electrode active body and a coating layer located on at least a portion of the surface of the positive electrode active material.
[0252] The elemental composition of the positive electrode active material in the positive electrode active layer can be analyzed by methods known in the art, including but not limited to the following methods: inductively coupled plasma spectroscopy (ICP), X-ray diffraction (XRD), single crystal X-ray diffraction (SCXRD), energy dispersive spectrometer (EDS), etc. The sample preparation methods and test methods of these test methods are known to those skilled in the art, and the test parameters can be appropriately adjusted according to the characteristics of the sample. The ICP method can be used to perform quantitative test analysis of the content of the components in the positive electrode active material.
[0253] To detect the positive electrode active material in the positive electrode active layer, after the battery is fully discharged, the battery cell is disassembled, the positive electrode plate is taken out, the material of the positive electrode active layer is scraped, and the type and proportion of elements are tested and analyzed using elemental analysis methods such as inductively coupled plasma (ICP) spectroscopy, thereby confirming the elemental composition and chemical formula of the positive electrode active material.
[0254] For positive electrode active materials or negative electrode active materials including a coating layer (an example of a coating layer is a carbon coating layer), the cross-section can be cut using FIB (focused ion beam) and the particle cross-sectional morphology can be observed under TEM (transmission electron microscope). A clear boundary can be observed at the coating interface, and the thickness and average thickness of the coating layer can be analyzed and calculated based on the TEM image. Further combined with one or more methods such as energy dispersive spectroscopy (EDS) analysis and Raman spectroscopy, the types of substances in the coating layer and the positive electrode active body can be confirmed, or the types of substances in the coating layer and the negative electrode active body can be confirmed.
[0255] Those skilled in the art can identify the components in the positive electrode active layer and the negative electrode active layer by one or more of the following detection methods known in the art, including but not limited to: Fourier transform infrared (FT-IR) spectroscopy, ultraviolet spectroscopy, nuclear magnetic resonance spectroscopy (HNMR), 1 H NMR) method, gel permeation chromatography (GPC) method, high performance liquid chromatography (HPLC) method, mass spectrometry, X-ray photoelectron spectroscopy (XPS) method, X-ray diffraction (XRD) method, Raman spectroscopy (Raman) method, single crystal X-ray diffraction (SCXRD) method, inductively coupled plasma spectroscopy (ICP) method, energy dispersive spectrometer (EDS) analysis, etc. The sample preparation methods and test methods of these test methods are known to those skilled in the art, and the test parameters can be appropriately adjusted according to the structure of the material or substance and the sample characteristics.
[0256] As a non-limiting example, EDS can be used to distinguish carbon from silicon, and then to distinguish carbon-based materials from silicon-based materials. For another example, EDS can be used to detect the type and content of the conductive agent, but is not limited thereto.
[0257] Taking the negative electrode active material including natural graphite and artificial graphite as a non-limiting example, natural graphite and artificial graphite can be distinguished by the appearance morphology of the particles; X-ray diffraction (XRD) analysis test can be further performed. In the XRD spectrum, if the characteristic peak near 2θ 26.5° is very sharp and has a high intensity, it is natural graphite; if the characteristic peak near 2θ 26.5° is relatively wide and has a weak intensity, it is artificial graphite.
[0258] Taking the negative electrode active materials including graphite and soft carbon as an example, Raman spectroscopy can be used to distinguish graphite and soft carbon; in more detail, the characteristic peak information of the carbon component in the spectrum (such as the intensity ratio of D peak / G peak, I D / G ) to analyze soft carbon. Both D peak and G peak are Raman characteristic peaks of carbon atom crystal. D peak represents the defects of carbon atom crystal. The more defects there are, the greater the intensity of D peak is. The intensity of D peak can reflect the content of amorphous (turbostratified stacking) area. G peak represents the in-plane stretching vibration of sp2 hybridization of carbon atoms. The intensity of G peak can reflect the content of graphitized (layered structure) area. As the degree of disorder of carbon atoms increases, the intensity ratio of D peak to G peak also increases. You can also compare Raman spectra I D / G Standard Raman spectrum of graphite I D / G The difference between the D peak and the G peak in the Raman spectrum can be used to distinguish between graphite and hard carbon. Similarly, the difference between the D peak and the G peak in the Raman spectrum can be used to distinguish between natural graphite and artificial graphite.
[0259] In some embodiments, the electrolyte satisfies one or more of the following characteristics:
[0260] (e1) the mass percentage of the first additive in the electrolyte is greater than 0 and less than or equal to 3.2%, and may be 0.01% to 3.2%, and may be further 0.05% to 1.6%, and may be any of the following percentages or a range consisting of any two of the following percentages: 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3%, 3.2%, etc.;
[0261] (e2) The mass ratio of the second additive to the first additive is 0.01-50, can be 0.1-30, further can be 0.5-25, further can be 1-20, and can also be any of the following values or a range consisting of any two of the following values: 0.01, 0.02, 0.025, 0.03, 0.033, 1 / 30, 0.04, 0.05, 0.075, 0.1, 0.2, 0.25, 0.3, 1 / 3, 0.4, 0.5, 0.6, 0.7, 0.75, 0.8, 0.9, 1, 1.1, 1.2, 1.25, 1.4, 1.5, 1.75, 1.8, 2, 2.25, 2.5, 2.75, 3, 3.3, 10 / 3, 3.5, 4, 5, 6, 8, 10, 15, 20, 22, 24, 25, 26, 28, 30, etc.
[0262] In some embodiments, the electrolyte satisfies one or more of the following characteristics:
[0263] (e1') The mass percentage of the first additive in the electrolyte is 0.05%~0.2%;
[0264] (e2') The mass ratio of the second additive to the first additive is 0.1 to 50.
[0265] By controlling the mass percentage of the first additive in the electrolyte within the aforementioned range, the first additive can continue to play a role in repairing the SEI film during fast charging and cycling, and can maintain better fast charging performance for a longer period of time.
[0266] By controlling the mass ratio of the second additive to the first additive within the aforementioned range, the first additive and the second additive can better exert a synergistic effect, which is beneficial for improving the negative electrode SEI film and inhibiting fast charging gas production while better inhibiting the increase in negative electrode interface impedance, thereby better improving the fast charging performance of lithium-ion secondary batteries.
[0267] By controlling the mass percentage of the first additive in the electrolyte and the mass ratio of the second additive to the first additive within the aforementioned range, it is beneficial to better exert the synergistic effect between the first additive and the second additive and better improve the fast charging performance of the lithium-ion secondary battery.
[0268] In some embodiments, the second additive includes one or more of a lithium salt additive, a phosphate ester additive, vinylene carbonate, a fluorocarbonate additive, a saturated sultone, and a cyclic sulfate;
[0269] In some embodiments, the electrolyte satisfies one or more of the following characteristics:
[0270] (f1) The lithium salt additive includes one or more of oxalate lithium salt, lithium tetrafluoroborate, lithium difluorophosphate and fluorosulfonic acid lithium salt; the oxalate lithium salt includes one or more of lithium difluorooxalatoborate (LiDFOB), lithium difluorodioxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP); the fluorosulfonic acid lithium salt includes one or more of lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI);
[0271] (f2) Phosphate additives include silicon-based phosphate additives; silicon-based phosphate additives include one or more of tris(trimethylsilyl)phosphate (TMSP) and tris(trimethylsilyl)phosphite (TMSPi);
[0272] (f3) Fluorinated carbonate additives including fluoroethylene carbonate (FEC);
[0273] (f4) Cyclic sulfates include one or more of monocyclic sulfates and polycyclic sulfates.
[0274] In the present application, "cyclic sulfate" contains one or more monocyclic sulfate units, and "monocyclic sulfate unit" contains *-OS(=O)2-O-*, where two *s each independently represent a bonding site to a carbon atom.
[0275] In some embodiments, the additive includes a polycyclic sulfate, which contains multiple monocyclic sulfate units.
[0276] In some embodiments, multiple monocyclic sulfate units in the polycyclic sulfate are linked in a chain-like manner.
[0277] In some embodiments, the number of monocyclic sulfate units in the polycyclic sulfate is 2 to 4, and further can be 2, 3 or 4.
[0278] In some embodiments, the monocyclic sulfate ester unit is a 5- to 7-membered monocyclic ring, which may be a 5-membered ring, a 6-membered ring or a 7-membered ring, and may further be a 5-membered ring or a 6-membered ring.
[0279] In some embodiments, the monocyclic sulfate unit is substituted by 0, 1 or more substituent groups Q3, and the substituent groups Q3 in the monocyclic sulfate unit are each independently halogen, C 1-3 Alkyl or C 1-3 Alternatively, the substituent groups Q3 in the monocyclic sulfate unit are each independently a fluorine atom, a methyl group or a methoxy group.
[0280] In some embodiments, the electrolyte satisfies one or more of the following characteristics:
[0281] (g1) The mass percentage of the lithium salt additive in the electrolyte is 0-3%, which can be 0.05%-3%, or any of the following percentages or a range consisting of any two of the following percentages: 0, 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, etc.;
[0282] (g2) the lithium salt additive includes lithium difluorooxalate borate. Without limitation, the mass percentage of lithium difluorooxalate borate in the electrolyte may be 0-3%, optionally 0.05%-3%, or any of the following percentages or a range consisting of any two of the following percentages: 0, 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, etc.;
[0283] (g3) lithium salt additives include lithium bis(fluorosulfonyl)imide;
[0284] (g4) the mass percentage of the phosphate additive in the electrolyte is 0-2%, which can be 0.1%-2%, or any of the following percentages or a range consisting of any two of the following percentages: 0, 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.75%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.25%, 1.3%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, etc.;
[0285] (g5) the mass percentage of vinylene carbonate in the electrolyte is 0-3%, which can be 0.1%-3%, or any of the following percentages or a range consisting of any two of the following percentages: 0, 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.75%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.25%, 1.3%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3%, etc.;
[0286] (g6) the mass percentage of the fluorocarbonate additive in the electrolyte is 0-10%, which can be 0.1%-10%, or any of the following percentages or a range consisting of any two of the following percentages: 0, 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.75%, 0.8%, 0.9%, 1%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.5%, 3%, 4%, 5%, 6%, 7%, 7.5%, 8%, 9%, 10%, etc.;
[0287] (g7) Fluorinated carbonate additives include fluoroethylene carbonate. In a non-limiting manner, the mass percentage of fluoroethylene carbonate in the electrolyte can be 0-10%, optionally 0-5%, 0.1%-10%, further optionally 0.1%-5%, 1%-10%, 1%-6%, further optionally 1%-5%, or any of the following percentages or a range consisting of any two of the following percentages: 0, 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1 %, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.75%, 0.8%, 0.9%, 1%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 7.5%, 8%, 9%, 10%, etc.;
[0288] (g8) the mass percentage of saturated sultone in the electrolyte is 0-3%, and can be 0.1%-3%, or any one of the following percentages or a range consisting of any two of the following percentages: 0, 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.75%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.25%, 1.3%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3%, etc.;
[0289] (g9) the mass percentage of cyclic sulfate in the electrolyte is 0-3%, which can be 0.1%-3%, or any of the following percentages or a range consisting of any two of the following percentages: 0, 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.75%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.25%, 1.3%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3%, etc.;
[0290] (g10) Cyclic sulfate includes polycyclic sulfate. Without limitation, the mass percentage of polycyclic sulfate in the electrolyte may be 0-3%, optionally 0.1%-3%, or any of the following percentages or a range consisting of any two of the following percentages: 0, 0.01%, 0.02%, 0.04%, 0.05%, 0.08%, 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0. 2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.75%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.25%, 1.3%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8%, 3%, etc.
[0291] By selecting the second additive to have the aforementioned type and / or amount, it is beneficial to better exert the competitive effect and synergistic effect between the first additive and the second additive, and better improve the battery performance.
[0292] For example, the negative electrode film-forming impedance of lithium salt additives and phosphate additives is low. By introducing one or more of lithium salt additives and phosphate additives into the electrolyte, it is beneficial to reduce the interfacial impedance of the negative electrode SEI film and improve the fast charging performance of lithium-ion secondary batteries.
[0293] For example, vinylene carbonate (VC) can optimize the SEI film. By introducing VC into the electrolyte, it is beneficial to reduce or delay the negative electrode film consumption of the first additive, and better control the charge transfer impedance on the negative electrode surface and the battery internal resistance.
[0294] For example, fluorocarbonate additives (such as fluoroethylene carbonate (FEC)) can form a relatively strong interface film with lower ion transfer impedance on the surface of the negative electrode at room temperature. By introducing fluorocarbonate additives (such as FEC) into the electrolyte, it is beneficial to reduce or delay the consumption of the first additive in the negative electrode film formation, and better control the negative electrode interface impedance and battery internal resistance.
[0295] For example, saturated sultones (such as 1,3-propane sultone (PS) etc.) can participate in the negative electrode film formation to form a dense and stable negative electrode SEI film, which is beneficial to reduce or delay the negative electrode film formation consumption of the first additive and better control the negative electrode interface impedance and battery internal resistance.
[0296] For example, by introducing cyclic sulfate into the electrolyte, the negative electrode interface film can be optimized, the stability of the negative electrode SEI film can be improved, the negative electrode interface side reactions can be reduced and gas production can be inhibited during fast charging, and the negative electrode interface impedance and battery internal resistance can be better controlled.
[0297] In some embodiments, the electrolyte includes one or both of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and in some embodiments, the electrolyte includes at least lithium hexafluorophosphate.
[0298] In some embodiments, the molar volume concentration of lithium bis(fluorosulfonyl)imide in the electrolyte is 0 to 0.5 mol / L, which can be 0.01 mol / L to 0.5 mol / L, or any of the following concentrations or a range selected from any two of the following concentrations: 0 mol / L, 0.01 mol / L, 0.02 mol / L, 0.025 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.075 mol / L, 0.08 mol / L, 0.09 mol / L, 0.1 mol / L, 0.12 mol / L, 0.14 mol / L, 0.15 mol / L, 0.16 mol / L, 0.18 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L, etc.
[0299] Lithium bis(fluorosulfonyl)imide can be used as a film-forming additive in the electrolyte and can also play the role of an electrolyte salt.
[0300] In the present application, when the mass percentage of the lithium salt additive (such as LiFSI) in the electrolyte is greater than 0.5%, the mass percentage of the lithium salt additive (such as LiFSI) in the second additive in the electrolyte is recorded as 0.5%.
[0301] In some embodiments, the electrolyte includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide. Without limitation, the molar volume concentration of lithium bis(fluorosulfonyl)imide in the electrolyte can be greater than 0 mol / L and less than or equal to 0.5 mol / L, and can be selected from 0.01 mol / L to 0.5 mol / L, and can also be selected from a suitable range or value in any embodiment of the context.
[0302] Lithium bis(fluorosulfonyl)imide (LiFSI) can participate in the formation of a stable solid electrolyte interface film at the positive and negative electrodes. On the one hand, by introducing LiFSI into the electrolyte, the stability of the positive and negative electrode interface films can be improved, and the electrolyte interface side reactions at the positive and negative electrodes can be reduced and gas production can be suppressed during fast charging. On the other hand, LiFSI has a better ability to dissociate lithium ions than lithium hexafluorophosphate (LiPF6), so the addition of LiFSI is also beneficial to improve the liquid phase conductivity. Therefore, by introducing LiFSI into the electrolyte, the fast charging performance of lithium-ion secondary batteries can be better improved.
[0303] In some embodiments, the electrolyte satisfies one or more of the following characteristics:
[0304] (h1) the molecular weight of the first additive is less than or equal to 500 Da;
[0305] (h2) the first additive contains 1 to 4 carbon-carbon triple bonds in the molecule. Without limitation, the number of carbon-carbon triple bonds in the molecule of the first additive may be 1, 2, 3 or 4;
[0306] (h3) The carbon-carbon triple bond in the first additive is CH≡C-;
[0307] (h4) The first additive includes one or more of a first alkynyl compound and a second alkynyl compound; wherein the first alkynyl compound contains a carbon-carbon triple bond and a Lewis base nitrogen heterocycle, the carbon-carbon triple bond and the Lewis base nitrogen heterocycle in the first alkynyl compound are connected by a linker L1, and the linker L1 contains a C covalently bonded to the carbon-carbon triple bond. 1-3 The second alkynyl compound contains a carbon-carbon triple bond and an alkyl carbonate group. The structure of the alkyl carbonate group is R2-OC(=O)-O-*, where * is the bonding site connected to the carbon atom, and R2 is C 1-3 Alkyl; the carbon-carbon triple bond in the second alkynyl compound and the alkyl carbonate group are connected by a linker L2, and the linker L2 contains a C covalently bonded to the carbon-carbon triple bond. 1-3 Alkylene.
[0308] In this application, unless otherwise specified, "Lewis base nitrogen heterocycle" refers to a nitrogen heterocycle with Lewis base properties. This concept is based on Lewis acids and bases theory. Lewis base nitrogen heterocycles can donate electron pairs and have electron-rich properties. Therefore, Lewis base nitrogen heterocycles can attract and bind acidic substances. Non-limiting examples of Lewis base nitrogen heterocycles include imidazole rings, but are not limited thereto.
[0309] In the present application, unless otherwise specified, "nitrogen heterocyclic structure" refers to a cyclic structure in which the ring-forming atoms include nitrogen atoms. The term "ring-forming atoms" refers to the constituent atoms of the ring skeleton. As a non-limiting example, the three carbon atoms and two nitrogen atoms in the imidazole ring are ring-forming atoms, and the imidazole ring is a 5-membered ring. "Ring-forming nitrogen atoms" refers to nitrogen atoms in the ring-forming atoms.
[0310] In this application, the term “C 1-3 "Alkylene", unless otherwise specified, may be methylene, ethylene or propylene, and may further be methylene, 1,2-ethylene or 1,3-propylene.
[0311] In this application, the term “C 1-3 "Alkyl", unless otherwise specified, may be methyl, ethyl or propyl, and may further be methyl, ethyl, n-propyl or isopropyl.
[0312] In some embodiments, R2 is methyl.
[0313] In some embodiments, the electrolyte satisfies one or more of the following characteristics:
[0314] (i1) the molecular weight of the first additive is less than or equal to 300 Da;
[0315] (i2) the first additive contains 1 to 4 Lewis base nitrogen heterocycles in the molecule. Without limitation, the number of Lewis base nitrogen heterocycles in the first additive may be 1, 2, 3 or 4;
[0316] (i3) Lewis base nitrogen heterocycles include substituted or unsubstituted imidazole groups, wherein the imidazole ring in the substituted or unsubstituted imidazole group is substituted by 0, 1 or more substituent groups Q2, and the substituent groups Q2 in the substituted imidazole group are each independently C 1-3 An alkyl group, a cyano group (-CN) or a fluorine atom; optionally, the substituent groups Q2 in the substituted imidazole group are each independently a methyl group, a cyano group or a fluorine atom;
[0317] (i4) The first alkynyl compound is composed of a carbon-carbon triple bond, C 1-3 Alkylene and -OC(=O)-R 10 Composition, R 10It is a Lewis base nitrogen heterocycle; the second alkynyl compound is composed of a carbon-carbon triple bond, C 1-3 Alkylene and -OC(=O)-OR 20 Composition, R 20 is an alkyl group, optionally C 1-3 alkyl.
[0318] In some embodiments, the first alkynyl compound can be composed of a carbon-carbon triple bond, a C 1-3 Alkylene and -OC(=O)-R 10 Composition, R 10 It is a Lewis base nitrogen heterocycle.
[0319] In some embodiments, the second alkynyl compound can be composed of a carbon-carbon triple bond, a C 1-3 Alkylene and -OC(=O)-OR 20 Composition, R 20 is an alkyl group, and may further be C 1-3 alkyl.
[0320] Without limitation, in the electrolyte, the sum of the mass proportions of the first additive in the acetylene additive can be greater than 50%, further can be 80%~100%, further can be 90%~100%, and can also be any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.
[0321] In some embodiments, the acetylene additive in the electrolyte is the first additive.
[0322] Without limitation, in the electrolyte, the sum of the mass proportions of the first alkynyl compound and the second alkynyl compound in the first additive may be greater than 50%, further may be 80% to 100%, further may be 90% to 100%, and may also be any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.
[0323] In some embodiments, in the electrolyte, the mass proportion of the first acetylenic compound in the first additive or the acetylenic additive can be 80% to 100%, further can be 90% to 100%, and can also be any of the following percentages or a range consisting of any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.
[0324] In some embodiments, in the electrolyte, the mass proportion of the second acetylenic compound in the first additive or the acetylenic additive can be 80% to 100%, further can be 90% to 100%, and can also be any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.
[0325] In some embodiments, in the electrolyte, the first additive is a combination of a first alkynyl compound and a second alkynyl compound. Further, the first additive may be the first alkynyl compound.
[0326] In some embodiments, the first alkynyl compound includes Compound II, and further may be Compound II. In some embodiments, the first additive is Compound II.
[0327] In some embodiments, the second alkynyl compound includes compound III, and further can be compound III. In some embodiments, the first additive is compound III.
[0328] In some embodiments, the first additive includes one or more of Compound II and Compound III.
[0329] In some embodiments, the first additive includes one or more of Compound IIa and Compound IIIa.
[0330] In some embodiments, the first additive includes one or more of Compound II and Compound III;
[0331] The structure of compound II is Among them, L 11 C 1-3 Alkylene, Q2 is independently C 1-3 Alkyl, cyano or fluorine atom, p2 is 0, 1, 2 or 3;
[0332] The structure of compound III is Among them, L 21 C 1-3 Alkylene, R 22 C 1-3 alkyl.
[0333] In some embodiments, L 11 For methylene.
[0334] In some embodiments, p2 is 0.
[0335] In some embodiments, L 21 For methylene.
[0336] In some embodiments, R 22 It is methyl.
[0337] In some embodiments, compound II is compound IIa ( ).
[0338] In some embodiments, compound III is , which can be recorded as compound IIIa.
[0339] In some embodiments, the first alkynyl compound includes compound IIa, and may further be compound IIa. In some embodiments, the first additive is compound IIa.
[0340] In some embodiments, the second alkynyl compound includes compound IIIa, and may further be compound IIIa. In some embodiments, the first additive is compound IIIa.
[0341] In some embodiments, in the electrolyte, the sum of the mass proportions of compound IIa and compound IIIa in the first additive can be 80% to 100%, further can be 90% to 100%, and can also be any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 92%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, etc.
[0342] In some embodiments, the electrolyte satisfies one or more of the following characteristics:
[0343] (j1) The first additive includes compound II. Without limitation, the mass proportion of compound II in the first additive may be 80% to 100%, optionally 90% to 100%, or any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.;
[0344] (j2) The first additive includes a structure of Compound IIa, without limitation, the mass proportion of compound IIa in the first additive can be 80% to 100%, optionally 90% to 100%, or any of the following percentages or a range selected from any two of the following percentages: 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.
[0345] By controlling the molecular weight of the first additive within the aforementioned lower range, the first additive can have a smaller molecular size, which is beneficial for better controlling the low viscosity characteristics of the electrolyte, making the electrolyte have a higher conductivity, and can better cooperate with the solvent of formula I to improve the battery dynamics.
[0346] By controlling the number of carbon-carbon triple bonds in the first additive within the aforementioned range, the first additive can better cooperate with the solvent of formula I to improve the fast charging performance of the lithium-ion secondary battery, and it is also beneficial to inhibit the increase in interfacial impedance caused by the first additive participating in the formation and repair of the SEI film, and it is also beneficial to control the influence of the first additive on the liquid phase impedance; thereby, the battery dynamics can be better improved, and the fast charging performance of the lithium-ion secondary battery can be better improved.
[0347] The first alkynyl compound includes both a carbon-carbon triple bond and a Lewis base nitrogen heterocycle, which can promote the formation of an organic / inorganic dual-property interface film in the process of participating in the negative electrode interface reaction, improve the stability of the negative electrode SEI film, and can better cooperate with the solvent of formula I to comprehensively improve the fast charging performance of lithium-ion secondary batteries; the Lewis base nitrogen heterocycle can also absorb acid by-products in the electrolyte, which is beneficial to improving the stability of the negative electrode interface and the negative electrode active material, reducing the consumption rate of the first additive, reducing the battery internal resistance growth rate, and maintaining a better fast charging performance for a longer period of time.
[0348] By controlling the amount of the Lewis base nitrogen heterocycle in the first additive within the aforementioned range, it is beneficial to better absorb the acid byproducts in the electrolyte, and it is also beneficial to control the steric effect of the Lewis base nitrogen heterocycle on the carbon-carbon triple bond.
[0349] Examples of Lewis base nitrogen heterocycles include the imidazole ring in compound II and compound IIa.
[0350] In some embodiments, the electrolyte satisfies one or more of the following characteristics:
[0351] The mass proportion of the solvent of formula (k1) I in the linear carboxylate compound can be 75% to 100%, optionally 90% to 100%, or any of the following percentages or a range consisting of any two of the following percentages: 75%, 76%, 78%, 80%, 82%, 84%, 85%, 86%, 88%, 90%, 94%, 95%, 96%, 98%, 100%, etc.;
[0352] (k2) The mass proportion of the linear carboxylic acid ester compound in the non-aqueous solvent may be 5% to 80%, optionally 10% to 60%, or any of the following percentages or a range consisting of any two of the following percentages: 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 50%, 60%, 70%, 75%, 80%, etc.;
[0353] (k3) The conductivity of the electrolyte at 25°C can be 9 mS / cm~25 mS / cm, and can be optionally 10 mS / cm~18 mS / cm. It can also be any of the following conductivities or a range consisting of any two of the following conductivities: 9 mS / cm, 10 mS / cm, 11 mS / cm, 12 mS / cm, 13 mS / cm, 14 mS / cm, 15 mS / cm, 16 mS / cm, 18 mS / cm, 20 mS / cm, 21 mS / cm, 22 mS / cm, 23 mS / cm, 24 mS / cm, 25 mS / cm, etc.
[0354] In some embodiments, the electrolyte satisfies one or more of the following characteristics:
[0355] (k1') The mass proportion of the solvent of formula I in the chain carboxylic acid ester compound is 90% to 100%;
[0356] (k2') The mass proportion of chain carboxylic acid ester compounds in the non-aqueous solvent is 10%~60%;
[0357] (k3') The conductivity of the electrolyte at 25°C is 10mS / cm~18mS / cm.
[0358] By controlling the mass proportion of the solvent of formula I in the chain carboxylic acid ester compound, the mass proportion of the chain carboxylic acid ester compound in the non-aqueous solvent, and one or more parameters of the conductivity of the electrolyte at 25°C within the aforementioned range, it is beneficial to better improve the battery dynamics, thereby helping to give the lithium-ion secondary battery better fast charging performance. Among them, the chain carboxylic acid ester compound such as (solvent of formula I) has a relatively low viscosity, which is beneficial to improve the conductivity of the electrolyte.
[0359] In this application, unless otherwise specified, the "conductivity" of the electrolyte refers to the ionic conductivity, which has a well-known meaning in the art and can be tested and analyzed using existing methods in the art. The ionic conductivity can be obtained by testing with a conductivity tester, such as a DDSJ-318 conductivity meter. The test temperature can be 25±0.1°C. The test can be performed with reference to the method of HG / T 4067-2015. Unless otherwise specified, the unit of the conductivity of the electrolyte is Siemens / cm (S / cm) or mS / cm.
[0360] Unless otherwise specified, the following steps may be used for testing:
[0361] Pretreatment: Take the standard liquid and keep it at a constant temperature of 25℃ (deviation ±0.1℃), and take the test liquid and keep it at a constant temperature of the test temperature (deviation ±0.1℃);
[0362] Test: Test the instrument with two standard solutions at 25°C. After calibration, clean the electrode and place the test sample electrode vertically into the liquid to be tested. Click to start the test and wait for the data to stabilize for more than 10 seconds to record the test results.
[0363] In some embodiments, the lithium ion secondary battery includes a lithium ion secondary battery cell.
[0364] In this application, unless otherwise specified, "battery cell" refers to a basic unit that can realize the mutual conversion of chemical energy and electrical energy, and further, generally speaking, at least includes a positive electrode sheet, a negative electrode sheet and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet.
[0365] The following is some description about the positive electrode.
[0366] The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active layer includes a positive electrode active material.
[0367] Without limitation, the weight percentage of the positive electrode active material in the positive electrode active layer may be greater than or equal to 80 wt %, and further may be greater than or equal to 90 wt %.
[0368] As a non-limiting example, the positive electrode current collector has two surfaces that are opposite to each other in its thickness direction, and the positive electrode active layer is disposed on any one or both of the two surfaces of the positive electrode current collector that are opposite to each other.
[0369] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. In the positive electrode current collector, the composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. In the positive electrode current collector, the composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. Non-limitingly, in the positive electrode current collector, the polymer material substrate may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0370] The positive electrode active material may be a positive electrode active material for a battery known in the art. These positive electrode active materials may be used alone or in combination of two or more.
[0371] In some embodiments, the positive electrode active material includes a lithium transition metal oxide. Examples of lithium transition metal oxides may include, but are not limited to, one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and modified compounds thereof. Non-limiting examples of lithium cobalt oxides may include LiCoO2; non-limiting examples of lithium nickel oxides may include LiNiO2; non-limiting examples of lithium manganese oxides may include LiMnO2, LiMn2O4, etc.; non-limiting examples of lithium nickel cobalt manganese oxides may include LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ) etc. Non-limiting examples of lithium nickel cobalt aluminum oxide may include LiNi 0.80 Co 0.15 Al 0.05 O2, etc.
[0372] The type of positive electrode active material can also be referred to the context of this application.
[0373] It is understandable that the battery will be accompanied by lithium (Li) deintercalation and consumption during the charging and discharging process, and the content of Li in the positive electrode sheet is different when the battery is discharged to different states. In the exemplary description of the positive electrode active material in this application, unless otherwise specified, the content of Li can be the initial state of the material or the non-initial state after the charge and discharge cycle. The positive electrode active material is applied to the positive electrode in the battery system, and after the charge and discharge cycle, the content of Li in the positive electrode active material at the positive electrode usually changes. Among them, the content of Li can be measured by atomic molar content, but is not limited to this. Regarding "the content of Li is the initial state of the material", the initial state of the material refers to the state before being made into a positive electrode active layer. It can be understood that the new material or new substance obtained by appropriately modifying the listed positive electrode active materials is also within the scope of the positive electrode active material. The aforementioned appropriate modification refers to the acceptable modification method for the positive electrode active material, and non-limiting examples include one or more of coating modification and doping modification.
[0374] In the exemplary description of the positive electrode active material in this application, the content of oxygen (O) is only a theoretical state value. The release of oxygen from the lattice will cause the atomic molar content of oxygen to change, and the actual content of O will fluctuate. Among them, the content of O can be measured by atomic molar content, but is not limited to this.
[0375] In some embodiments, the positive electrode active layer may optionally include a binder. As a non-limiting example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin. Typically, the weight percentage of the binder in the positive electrode active layer may be 0 to 10 wt%, further 0 to 8 wt%, and further 1 wt% to 5 wt%, based on the total weight of the positive electrode active layer.
[0376] In some embodiments, the positive electrode active layer optionally includes a conductive agent. As a non-limiting example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. Typically, the weight percentage of the conductive agent in the positive electrode active layer may be 0 to 10 wt%, further 0 to 8 wt%, and further 0 to 5 wt%, based on the total weight of the positive electrode active layer.
[0377] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent to form a positive electrode slurry. Further, the positive electrode slurry is coated on at least one side of the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained. Cold pressing can be performed by a cold rolling mill. The type of solvent in the positive electrode slurry can include but is not limited to any of the aforementioned embodiments, for example, it can include N-methylpyrrolidone (NMP), and further can be NMP. The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector, or on both surfaces of the positive electrode collector. The solid content of the positive electrode slurry can be 40wt%~80wt%. The viscosity of the positive electrode slurry at room temperature can be adjusted to 5000mPa·s~25000mPa·s.
[0378] In some embodiments, the positive electrode active material includes a lithium-containing phosphate positive electrode material. Further, the mass proportion of the lithium-containing phosphate positive electrode material in the positive electrode active material can be greater than or equal to 50%, can be 100%, but is not limited thereto. When the positive electrode slurry is coated, the coating surface density (based on the coating surface density on one side) on a dry weight basis (excluding the solvent) can also be (0.1 ~ 0.5) g / 1540.25 mm 2 , but not limited to this. The compaction density of the positive electrode sheet can be 2.0g / cm 3 ~2.8 g / cm 3 , optional 2.3g / cm 3 ~2.6 g / cm 3 .
[0379] In some embodiments, the positive electrode active material includes a lithium composite metal oxide positive electrode material, and further, the mass proportion of the lithium composite metal oxide positive electrode material in the positive electrode active material can be greater than or equal to 50%, and further can be 95% to 100%, but is not limited thereto. When coating the positive electrode slurry, the coating surface density (measured by the coating surface density on one side) based on dry weight (excluding the solvent) can be (0.05 to 0.6) g / 1540.25 mm 2 , optional: (0.1~ 0.3) g / 1540.25mm 2 The compaction density of the positive electrode sheet can be 3.0 g / cm 3 ~ 4.2 g / cm 3 , optional 3.3 g / cm 3 ~ 3.8 g / cm 3 .
[0380] The "compacted density" used in this application has a well-known meaning in the art and is one of the reference indicators of material energy density. In this application, unless otherwise specified, the compacted density of the positive electrode sheet refers to the ratio of the mass of the positive electrode active layer to its volume, and the compacted density of the negative electrode sheet refers to the ratio of the mass of the negative electrode active layer to its volume.
[0381] The following are some additional descriptions about the negative electrode.
[0382] The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active layer includes a negative electrode active material.
[0383] Without limitation, the weight percentage of the negative electrode active material in the negative electrode active layer may be greater than or equal to 80 wt %, and further may be greater than or equal to 90 wt %.
[0384] As a non-limiting example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode active layer is disposed on any one or both of the two surfaces facing each other of the negative electrode current collector.
[0385] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. In the negative electrode current collector, the composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. In the negative electrode current collector, the composite current collector may be formed by forming a metal material on a polymer material substrate. In the negative electrode current collector, non-limiting examples of the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In a non-limiting manner, in the negative electrode current collector, the polymer material substrate may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0386] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As a non-limiting example, the negative electrode active material may include one or more of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. Silicon-based materials may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials or substances, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0387] In some embodiments, the negative electrode active layer may optionally include a binder. Without limitation, the binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS). Without limitation, the weight percentage of the binder in the negative electrode active layer may be 0wt% to 20wt%, further 0wt% to 10wt%, further 0 to 5wt%, further 1wt% to 5wt%, and further 1wt% to 3wt%.
[0388] The type of negative electrode active material can also be referred to the context of this application.
[0389] In some embodiments, the negative electrode active layer may optionally include a conductive agent. In a non-limiting manner, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In a non-limiting manner, the weight percentage of the conductive agent in the negative electrode active layer may be 0wt% to 15wt%, further optionally 0wt% to 10wt%, and further optionally 0wt% to 5wt%.
[0390] In some embodiments, the negative electrode active layer may optionally include other additives, such as a thickener (e.g., sodium carboxymethyl cellulose (CMC-Na)). In a non-limiting manner, the weight percentage of other additives in the negative electrode active layer may be 0 wt% to 15 wt%, further 0 wt% to 10 wt%, further 0 wt% to 5 wt%, further 0 wt% to 3 wt%, and further 0 wt% to 2 wt%.
[0391] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry. Further, the negative electrode slurry is coated on at least one side of the surface of the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. Cold pressing can be performed using a cold rolling mill. The surface of the negative electrode collector coated with the negative electrode slurry can be on a single surface of the negative electrode collector or on both surfaces of the negative electrode collector. The solid content of the negative electrode slurry can be 30 wt%~70wt%, and can be optionally 40wt%~60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000 mPa·s~10000 mPa·s, and can be optionally 3000 mPa·s~10000 mPa·s. When coating the negative electrode slurry, the coating surface density on one side of the negative electrode current collector can be 7.5 mg / cm based on dry weight (excluding solvent). 2 ~22 mg / cm 2 , optional: (0.12~0.2)g / 1540.25mm 2 The compaction density of the negative electrode sheet can be 1.0 g / cm 3 ~ 2.0g / cm 3 , optional 1.0 g / cm 3 ~ 1.8 g / cm 3 .
[0392] The electrolyte is exemplarily described below.
[0393] The electrolyte has the function of conducting ions between the positive electrode and the negative electrode. The electrolyte includes electrolyte salt and solvent.
[0394] In some embodiments, the electrolyte is a non-aqueous electrolyte. The non-aqueous electrolyte may include an electrolyte salt and a non-aqueous solvent.
[0395] Without limitation, the concentration of the electrolyte salt in the electrolyte solution can generally be 0.5 mol / L to 5 mol / L, optionally 0.5 mol / L to 2 mol / L, and can also be any of the following concentrations or a range consisting of any two of the following concentrations: 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.8 mol / L, 2 mol / L, etc. The electrolyte salt of the non-aqueous solvent in the electrolyte solution can refer to the description in the context of this application.
[0396] In some embodiments, the electrolyte salt includes an electrolyte lithium salt, and may further be an electrolyte lithium salt. Without limitation, other types of electrolyte salts may also be introduced into the electrolyte.
[0397] In some embodiments, the electrolyte salt includes an electrolyte lithium salt. Without limitation, the electrolyte lithium salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorobisoxalatophosphate (LiDFOP), and lithium tetrafluorooxalatophosphate (LiTFOP).
[0398] The type of non-aqueous solvent in the electrolyte can refer to the description in the context of this application. Without limitation, other types of non-aqueous solvents can also be introduced into the electrolyte. In some embodiments, the non-aqueous solvent can also include ethylene carbonate (EC, ), propylene carbonate (PC, )、ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC, ), one or more of 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0399] The electrolyte includes additives, including at least the first additive mentioned above.
[0400] The types of additives in the electrolyte can refer to the description in the context of this application. Without limitation, other types of additives can also be introduced into the electrolyte. Other types of additives can include negative electrode film-forming additives, positive electrode film-forming additives, and can also include additives that can improve certain properties of the battery, such as additives that improve the overcharge performance of the battery, additives that improve the high temperature or low temperature performance of the battery, etc.
[0401] The separator is exemplarily described below.
[0402] In some embodiments, the lithium-ion secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0403] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0404] In some embodiments, the thickness of the isolation film is 6 μm to 40 μm, and optionally 6 μm to 20 μm.
[0405] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0406] In some embodiments, the lithium-ion secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0407] In some embodiments, the outer packaging of the lithium ion secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the lithium ion secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and further, non-limiting examples of plastic can include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0408] A lithium-ion secondary battery includes at least one battery cell. A lithium-ion secondary battery may include one or more battery cells.
[0409] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.
[0410] In some embodiments, reference Figure 2 , the outer packaging may include a battery case 51 and a cover plate 53. Among them, the battery case 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The battery case 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to actual needs. In some embodiments, the injection coefficient of the electrolyte is greater than or equal to 1.6g / Ah.
[0411] The lithium-ion secondary battery may be a battery device 4 or a battery pack 1 .
[0412] The battery device includes at least one battery cell. The number of battery cells contained in the battery device can be one or more, and those skilled in the art can select a suitable number according to the application and capacity of the battery device.
[0413] Figure 3 4 is an example of a battery device. Figure 3 In the battery device 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery device 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0414] Optionally, the battery device 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0415] In some embodiments, the battery devices described above may also be assembled into a battery pack. The number of battery devices contained in the battery pack may be one or more. Those skilled in the art may select a suitable number according to the application and capacity of the battery pack.
[0416] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery devices 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery devices 4. The plurality of battery devices 4 can be arranged in the battery box in any manner.
[0417] In a second aspect of the present application, a method for preparing a lithium ion secondary battery is provided, which can be used to prepare the lithium ion secondary battery of the first aspect of the present application.
[0418] In some embodiments, a method for preparing a lithium-ion secondary battery is provided, comprising the following steps: allowing an electrode assembly including a positive electrode sheet, a separator and a negative electrode sheet to stand and soak in an electrolyte for chemical formation.
[0419] In some embodiments, a method for preparing a lithium ion secondary battery is provided, comprising the following steps:
[0420] S100: placing an electrode assembly including a positive electrode sheet, a separator and a negative electrode sheet in a battery housing; wherein a separator is provided between the positive electrode sheet and the negative electrode sheet;
[0421] S200: injecting electrolyte into the battery housing, and allowing the electrolyte to soak the positive electrode sheet and the negative electrode sheet to form; wherein the electrolyte includes electrolyte salt, non-aqueous solvent and additives; the non-aqueous solvent includes chain carboxylic acid ester compounds, the chain carboxylic acid ester compounds include formula I solvents, and the structure of the formula I solvent is shown in formula (I): In formula (I), R 11 and R 12 Each independently is a methyl group or an ethyl group; the additives are a first additive and a second additive, the first additive is a non-ionic organic additive containing a carbon-carbon triple bond, and the second additive is a negative electrode film-forming additive different from the first additive.
[0422] The prepared lithium ion secondary battery has the advantages of the lithium ion secondary battery described in the first aspect of the present application, and has improved fast charging performance, which will not be described in detail here.
[0423] In some embodiments, in step 200, after injecting electrolyte into the battery casing, a lithium-ion secondary battery assembly is obtained.
[0424] In some embodiments, the lithium-ion secondary battery assembly may correspond to a state before a formation treatment is performed.
[0425] Without limitation, the formation temperature may be 45° C., but is not limited thereto.
[0426] In some embodiments, the formation can be performed at 45° C. using a method comprising the following steps (steps S1, S2, S3 and S4 are performed in sequence):
[0427] S1) Charge at 0.05C for 14 minutes to 3V, and let stand for 10 minutes;
[0428] S2) Charge at 0.1C to 3.4V and let stand for 10 minutes;
[0429] S3) Charge at 0.2C to 3.65V and let stand for 10 minutes;
[0430] S4) Charge at 0.2C to 3.75V and let stand for 10 minutes;
[0431] End of transformation.
[0432] In the present application, the concentrations of additives and electrolyte salts involved in "injecting electrolyte into the battery casing" correspond to "initial concentrations", which may correspond to the initial mass proportion of the additives in the electrolyte and the initial molar volume concentration of the electrolyte salt in the electrolyte, respectively. Similarly, it also involves the initial mass proportion of the solvent of formula I in the chain carboxylate compound and the initial mass proportion of the chain carboxylate compound in the electrolyte.
[0433] In some embodiments, in the step of injecting electrolyte into the battery housing, the initial mass percentage of the first additive in the electrolyte is 0.1%~5%, which can be optionally 0.1%~3%, or any of the following percentages or a range consisting of any two of the following percentages: 0.1%, 0.12%, 0.14%, 0.15%, 0.16%, 0.18%, 0.2%, 0.22%, 0.24%, 0.25%, 0.26%, 0.28%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.6%, 0.75%, 0.8%, 0.9%, 1%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.
[0434] Those skilled in the art know that after the formation treatment, the content of some additive components in the electrolyte may change. As a non-limiting example, for example, some film-forming additive components are reduced in content due to their participation in the formation of the solid electrolyte interface film of the positive electrode and / or the negative electrode. As a non-limiting example, the content of the first additive in the electrolyte is generally reduced after the formation treatment relative to the electrolyte before the formation treatment.
[0435] In some embodiments, after the formation treatment, in the prepared lithium ion secondary battery, the content of each additive can refer to the first aspect of the present application.
[0436] In the lithium-ion secondary battery assembly, the types of electrolyte salt and non-aqueous solvent in the electrolyte can refer to the first aspect of the present application. After the chemical formation treatment, the mass proportions of the electrolyte salt and the solvent in the electrolyte may change.
[0437] In the lithium-ion secondary battery assembly, the material composition and size of the positive electrode sheet, the negative electrode sheet and the separator can refer to the first aspect of the present application. The size of the positive electrode sheet, the negative electrode sheet and the separator in the lithium-ion secondary battery assembly may be slightly different from the size in the lithium-ion secondary battery of the first aspect.
[0438] In some embodiments, the lithium ion secondary battery described in the first aspect of the present application is prepared.
[0439] In some embodiments of the third aspect of the present application, an electrical device is provided, comprising at least one of the lithium ion secondary battery described in the first aspect of the present application and the lithium ion secondary battery prepared by the preparation method of the lithium ion secondary battery described in the second aspect of the present application.
[0440] An electrical device including the aforementioned lithium ion secondary battery may have the advantages of the aforementioned lithium ion secondary battery, including but not limited to having improved fast charging performance.
[0441] In some embodiments, an electric device includes a lithium-ion secondary battery according to any embodiment of the present application.
[0442] Lithium-ion secondary batteries can be used as power sources for electrical devices, or as energy storage units for electrical devices. Electrical devices may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. Among them, mobile devices may be, for example, mobile phones, laptop computers, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, electric motorcycles, electric tools, etc., but are not limited thereto. The electrical device may also be used in fields such as aerospace, and may also be used in energy storage power supply systems such as hydropower, thermal power, wind power and solar power stations.
[0443] As an electrical device, a lithium-ion secondary battery can be selected according to its usage requirements.
[0444] Figure 6 The power consumption device 6 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of lithium-ion secondary batteries, a battery device or a battery pack can be used.
[0445] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a lithium-ion secondary battery may be used as a power source.
[0446] In a fourth aspect of the present application, a lithium-ion secondary battery assembly is provided, which is the lithium-ion secondary battery assembly in the method for preparing the lithium-ion secondary battery described in the second aspect of the present application.
[0447] In a fifth aspect of the present application, there is provided a use of the lithium-ion secondary battery described in the first aspect of the present application in supplying electric energy and / or storing electric energy.
[0448] The application includes a process of charging a lithium-ion secondary battery at a rate greater than or equal to 2C, that is, the lithium-ion secondary battery can provide a charging rate greater than or equal to 2C.
[0449] In this application, unless otherwise specified, the "rate" of a battery has a well-known meaning in the art, which refers to the current value required for the battery to charge to its rated capacity or discharge its rated capacity within a specified time, and the unit is expressed in C. Unless otherwise specified, the "specified time" is 1 hour (h), 1C means that charging and discharging are completed in 1 hour, and 1 / 3C means that charging and discharging are completed in 3 hours. The battery rate reflects the charging and discharging capabilities of the battery under different currents. A high rate means that the battery can charge and discharge quickly in a short time. The higher the rate, the better the fast charging performance.
[0450] In this application, unless otherwise specified, for the rate, "1C" means the current value required to charge the battery from zero to full or from full to empty within 1 hour. For the charging rate, when charging from zero at a rate of 1C, the battery will be fully charged in 1 hour.
[0451] In some embodiments, the application includes a process of charging a lithium ion secondary battery under at least one rate condition of 2C-6C, that is, the lithium ion secondary battery can provide a charging rate of 2C-6C.
[0452] In some embodiments, the application includes a process of charging a lithium-ion secondary battery under at least one rate condition of 2C-4C.
[0453] In some embodiments, the application includes a process of charging a lithium-ion secondary battery under at least one rate condition of 4C-6C.
[0454] Without limitation, the lithium-ion secondary battery can be charged at any of the following rates, or can be charged at a rate greater than or equal to any of the following rates, or can be charged at a rate within a range consisting of any two of the following rates: 2C, 3C, 4C, 5C, 6C, etc.
[0455] In some embodiments, the lithium-ion secondary battery can provide a charge rate greater than or equal to 2C.
[0456] In some embodiments, the lithium-ion secondary battery can provide a charge rate of 2C to 6C.
[0457] In the present application, “capable of providing a charging rate Cx” means that the battery cell can be charged under the condition of a charging rate Cx; for example, it can be charged to 97% SOC, but is not limited to this SOC state.
[0458] In some embodiments, the maximum charge rate of the lithium ion secondary battery may be greater than or equal to 2C, and may be 2C to 6C, and may be further 2C to 4C or 4C to 6C.
[0459] In some embodiments, the maximum charge rate of the lithium-ion secondary battery can be greater than 2C (C max >2C), can be greater than 2C and less than or equal to 6C (2 <C max ≤6C), and can further be greater than 2C and less than or equal to 4C (2 <C max ≤4C) or can be greater than or equal to 4C and less than or equal to 6C (4C≤C max ≤6C).
[0460] Without limitation, the maximum charge rate of the lithium-ion secondary battery may also be any one of the following charge rates or a range consisting of any two of the following charge rates: 2C, 3C, 4C, 5C, 6C, etc.
[0461] In this application, the maximum charge rate (which can be recorded as C) of a lithium-ion secondary battery is max )” has a well-known meaning in the industry and can be obtained by testing using conventional methods in the art. For example, the lithium precipitation window curve can be obtained by testing at different charging rates, and the critical charging rate at which lithium precipitation occurs is used as the test value of the maximum charging rate of the battery. The test parameters can be as follows: the battery to be tested is charged to a voltage of 3.8V at different rates (such as 1C, 2C, 2.5C, 3C, 3.5C, 4C, ...) at a constant current, then charged at a constant voltage to a current ≤0.05C, left to stand for 5 minutes, and then charged to 3.8V at a constant current rate of 0.33C, left to stand for 5 minutes, and the battery is disassembled to observe the lithium precipitation of the negative electrode. Exemplarily, a series of parallel samples can be prepared, starting from 1C, and tested at intervals of 0.1C until lithium precipitation occurs at the negative electrode. In order to reduce the amount of samples, a large interval can be selected to determine the range of the maximum charging rate, and then a small interval can be selected to more accurately determine the maximum charging rate. The intervals of the rate can be selected from 1C, 0.5C, 0.2C, and 0.1C, respectively.
[0462] Below, some embodiments of the present application are described. The described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The embodiments described below are exemplary and are only used to explain the present application, and should not be understood as limitations on the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0463] If the techniques or conditions are not specified in the examples, the above description, or the techniques or conditions described in the literature in the field, or the product instructions are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially, or can be synthesized in a conventional manner from commercially available products.
[0464] In the following examples, room temperature refers to 20°C to 30°C.
[0465] In the following examples, unless otherwise specified, the parameters involved can be confirmed by referring to the test methods described above. v 50. D v 10. D v 1, etc., parameters related to particle size, the average particle size of primary particles in the negative electrode active material (D1), the conductivity of the electrolyte, parameters related to the coating amount (such as the mass percentage of the coating layer), etc.
[0466] 1. Preparation of lithium-ion secondary batteries
[0467] Example 1.
[0468] (1) Positive electrode sheet: The positive electrode active material (carbon-coated lithium iron phosphate), conductive agent carbon black (Super P) and binder polyvinylidene fluoride (PVDF) are mixed evenly in a solvent N-methylpyrrolidone (NMP) at a weight ratio of 96:2:2 to obtain a positive electrode slurry with a solid content of 60wt%. The positive electrode slurry is coated on both sides of the positive electrode current collector aluminum foil, and the coating surface density on one side is 0.18g / 1540.25mm 2 , through drying, cold pressing, slitting, cutting and other processes, the positive electrode sheet is obtained. The compaction density of the positive electrode sheet is about 2.50g / cm 3 .
[0469] In this example, the positive electrode active material is a lithium phosphate-containing positive electrode material, further a lithium iron phosphate-based positive electrode material, further a soft carbon-coated lithium iron phosphate, which can be recorded as "carbon-coated LFP"; the soft carbon-coated lithium iron phosphate includes lithium iron phosphate and a soft carbon coating layer located on the surface of the lithium iron phosphate, and the mass proportion of the soft carbon coating layer in the soft carbon-coated lithium iron phosphate is approximately 1%.
[0470] The D of positive electrode active material v 10 and D v 50 are 0.4μm and 1.2μm respectively, see Table 1.
[0471] (2) Negative electrode sheet: The negative electrode active material (carbon-based material), conductive agent carbon black (Super P), binder styrene-butadiene rubber (SBR) and thickener sodium carboxymethyl cellulose (CMC-Na) were mixed in a solvent deionized water at a mass ratio of 97.0:1.2:1.0:0.8, with a solid content of 48wt%, to obtain a negative electrode slurry; the negative electrode slurry was coated on both sides of the negative electrode current collector copper foil, and the coating surface density on one side was 0.13g / 1540.25mm 2 Through drying, cold pressing, slitting and cutting processes, the negative electrode sheet is obtained. The compaction density of the negative electrode sheet is 1.65g / cm 3 .
[0472] In this example, the negative electrode active material is a carbon-based material, further a coated graphite (the negative electrode active body is artificial graphite, and a soft carbon coating layer is provided on the surface, and the mass proportion of the soft carbon coating layer in the coated graphite is about 2%). v 1 and D v 50 are 4.7μm and 12.1μm respectively, and the average particle size of the primary particles is about 0.8μm, as can be seen in Table 1.
[0473] (3) Isolation film:
[0474] A polyethylene (PE) film with a thickness of 13 μm was used.
[0475] (4) Preparation of electrolyte:
[0476] Add additives to the non-aqueous solvent, mix them evenly, then add fully dried electrolyte lithium salt, mix them thoroughly to fully dissolve the electrolyte lithium salt, and prepare an electrolyte solution.
[0477] The electrolyte salt in the electrolyte is an electrolyte lithium salt, and further, the electrolyte lithium salt is lithium hexafluorophosphate, and the initial concentration of lithium hexafluorophosphate in the electrolyte is 1 mol / L; the non-aqueous solvent is ethyl acetate, ethyl methyl carbonate (EMC) and ethylene carbonate (EC) in a mass ratio of 5:2:3; the additives are 2-propyn-1-yl 1H-imidazole-1-carboxylate (as a first additive) and fluoroethylene carbonate (FEC), the structure of the first additive is shown in formula (IIa), also recorded as compound IIa, the initial mass proportion of compound IIa in the electrolyte is 3wt%, and the initial concentration of FEC in the electrolyte is 2.5%.
[0478]
[0479] In Example 1, the solvent of formula I is ethyl acetate; the chain carboxylate compound is composed of the solvent of formula I, the mass proportion of the solvent of formula I in the chain carboxylate compound is 100%, and the mass proportion of the chain carboxylate compound in the non-aqueous solvent is 50%.
[0480] (5) Preparation of lithium-ion secondary batteries: stack and wind the positive electrode sheet, separator and negative electrode sheet in order to obtain a bare cell (electrode assembly); weld the tabs to the bare cell, place the bare cell into an aluminum shell, and bake it at 80°C to remove water. Then inject electrolyte and seal it. Then, go through the steps of standing, hot and cold pressing, formation, shaping, capacity testing, etc. to obtain a lithium-ion secondary battery.
[0481] After injecting the electrolyte, a lithium-ion secondary battery assembly is obtained.
[0482] In this example, the static infiltration parameters are: 18 hours at room temperature and then 6 hours at 45°C.
[0483] In this example, the formation parameters are as follows: at 45°C,
[0484] 0.05C charge for 14 minutes to 3.0V, let stand for 10 minutes;
[0485] 0.1C charge to 3.4V and let stand for 10 minutes;
[0486] 0.2C charge to 3.65V, let stand for 10min;
[0487] 0.2C charge to 3.75V, let stand for 10min;
[0488] The transformation is finished.
[0489] Example 2-3. A lithium-ion secondary battery was prepared by the same method as in Example 1, except that the electrolyte composition was different, the composition of the non-aqueous solvent in the electrolyte was different, the types of the chain carboxylic acid ester compound and the solvent of formula I were changed, and the remaining steps were the same as in Example 1. See Table 1.
[0490] In Example 2, the non-aqueous solvent is ethyl acetate:methyl acetate:ethyl methyl carbonate (EMC):ethylene carbonate (EC) in a mass ratio of 3:2:2:3.
[0491] In Example 3, the non-aqueous solvent is methyl acetate:ethyl methyl carbonate (EMC):ethylene carbonate (EC) in a mass ratio of 5:2:3.
[0492] Example 4-5. A lithium-ion secondary battery was prepared by the same method as in Example 1, except that the prepared electrolyte composition was different, the composition of the non-aqueous solvent in the electrolyte was different, the mass proportion of the chain carboxylic acid ester compound in the non-aqueous solvent was changed, and the remaining steps were the same as in Example 1. See Table 1.
[0493] In Example 4, the mass ratio of the chain carboxylic acid ester compound (ethyl acetate) in the non-aqueous solvent is 10%, and the mass ratio of ethyl methyl carbonate (EMC) to ethylene carbonate (EC) is the same as that in Example 1.
[0494] In Example 5, the mass ratio of the chain carboxylic acid ester compound (ethyl acetate) in the non-aqueous solvent is 80%, and the mass ratio of ethyl methyl carbonate (EMC) to ethylene carbonate (EC) is the same as that in Example 1.
[0495] Example 6 A lithium-ion secondary battery was prepared by using a method substantially the same as that of Example 1, except that in the step of preparing the positive electrode sheet, the particle size distribution of the positive electrode active material used was different, and the remaining steps were the same as those of Example 1. See Table 1.
[0496] In Example 6, the positive electrode active material D v 10 and D v 50 are 0.5μm and 1.4μm respectively.
[0497] Example 7 A lithium-ion secondary battery was prepared by using a method substantially the same as that of Example 1, except that in the step of preparing the negative electrode sheet, the particle size distribution of the negative electrode active material used was different, and the remaining steps were the same as those of Example 1. See Table 1.
[0498] In Example 7, the negative electrode active material D v 1 and D v 50 are 6.9 μm and 14.2 μm respectively, and the average particle size of the primary particles is 1.18 μm.
[0499] Example 8-9. A lithium ion secondary battery was prepared by a method substantially the same as that of Example 1, except that the prepared electrolyte composition was different, the initial mass proportion of the first additive in the electrolyte was different, and the remaining steps were the same as those of Example 1. See Table 1.
[0500] In Example 8, the initial mass proportion of the first additive (Compound IIa) in the electrolyte is 0.1%, and the initial mass proportion of FEC is 2%.
[0501] In Example 9, the initial mass proportion of the first additive (Compound IIa) in the electrolyte is 5%, and the initial mass proportion of FEC is 3%.
[0502] Example 10. A lithium ion secondary battery was prepared by a method substantially the same as that of Example 1, except that: the composition of the prepared electrolyte was different, the composition of the non-aqueous solvent in the electrolyte was different, the additive was increased by 1% by weight of PS (1,3-propylene sultone), the initial weight of FEC was 2%, and the remaining steps were the same as those of Example 1. See Table 1.
[0503] Examples 11-15 A lithium ion secondary battery was prepared by a method substantially the same as that of Example 1, except that the composition of the prepared electrolyte was different, the composition of the additive in the electrolyte was different, and the remaining steps were the same as those of Example 1. See Table 1.
[0504] In Example 11, the additives in the electrolyte are 1% of the first additive, 1% of the bicyclic sulfate (which can be recorded as "di-DTD") and 2% of FEC, based on the initial mass percentage in the electrolyte. The structure of the first additive is .
[0505] In Example 12, the additives in the electrolyte were 1% of the first additive, 1% of lithium difluorophosphate, and 2% of FEC, based on the initial mass percentage in the electrolyte.
[0506] In Example 13, the additives in the electrolyte were 1% of the first additive, 1% of LiDFOB (lithium difluorooxalatoborate), and 2% of FEC, based on the initial mass percentage in the electrolyte.
[0507] In Example 14, the additives in the electrolyte were 1% of the first additive, 0.5% of TMSP (tris(trimethylsilyl)phosphate) and 2% of FEC, based on the initial mass percentage in the electrolyte.
[0508] In Example 15, the additives in the electrolyte were 1% of the first additive, 1% of LiDFOB, and 2% of VC (vinylene carbonate), based on the initial mass percentage in the electrolyte.
[0509] Example 16 A lithium ion secondary battery was prepared by a method substantially the same as that of Example 1, except that the prepared electrolyte composition, the electrolyte additive composition and the electrolyte lithium salt composition were different, and the remaining steps were the same as those of Example 1. See Table 1.
[0510] In Example 16, the additives in the electrolyte are 1% of the first additive, 1% of "di-DTD", 1% of LiDFOB and 2% of VC (vinylene carbonate) based on the initial mass percentage in the electrolyte; the electrolyte lithium salt is 0.3 mol / L LiFSI (lithium bis(fluorosulfonyl)imide) and 0.7 mol / L LiPF6 (lithium hexafluorophosphate) based on the initial molar volume concentration in the electrolyte.
[0511] Example 17 A lithium ion secondary battery was prepared by using a method substantially the same as that of Example 1, except that the prepared electrolyte composition was different, the type of the first additive in the electrolyte was different, and the remaining steps were the same as those of Example 1. See Table 1.
[0512] In Example 17, the first additive compound IIa is replaced by methyl carboxylic acid-2-propynyl ester ( ).
[0513] Example 18 A lithium-ion secondary battery was prepared by using a method substantially the same as that of Example 4, except that in the step of preparing the negative electrode sheet, the negative electrode active material was different, and the remaining steps were the same as those of Example 4. See Table 1.
[0514] In Example 18, the negative electrode active material is a carbon-based material and a silicon-based material in a mass ratio of 95:5, that is, the mass ratio of the silicon-based material in the negative electrode active material is 5%. The carbon-based material is the same as in Example 1; the silicon-based material is a silicon-carbon composite material, including a porous carbon matrix and elemental silicon deposited in the pores of the porous carbon matrix, and the mass ratio of silicon element to carbon element is 1:1. v 1 and D v 50 is close to that in Example 1.
[0515] Example 19. A lithium-ion secondary battery was prepared by the same method as in Example 1, except that: in the step of preparing the positive electrode sheet, the positive electrode active material was different, and the coating surface density on one side of the positive electrode current collector was 0.27 g / 1540.25 mm 2 The compaction density of the positive electrode sheet is adjusted to 3.4g / cm 3 The coating surface density on one side of the negative electrode current collector is 0.16g / 1540.25mm 2 The compaction density of the negative electrode is 1.65g / cm 3 The remaining steps are the same as those in Example 1. Please refer to Table 1.
[0516] In Example 19, the positive electrode active material is a ternary positive electrode material NCM622 (LiNi 0.6 Co 0.2 Mn 0.2 O2).
[0517] The D of positive electrode active material v 10 and D v 50 are 1.8μm and 6.2μm respectively, see Table 1.
[0518] Comparative Example 1. A lithium ion secondary battery was prepared by using a method substantially the same as that of Example 1, except that the prepared electrolyte composition was different, the first additive was omitted from the electrolyte, and the initial concentration of the electrolyte lithium salt remained unchanged. The remaining steps were the same as those of Example 1.
[0519] Comparative Example 2 A lithium ion secondary battery was prepared by using a method substantially the same as that of Example 16, except that the prepared electrolyte composition was different, the first additive was omitted from the electrolyte, and the initial concentration of the electrolyte lithium salt remained unchanged. The remaining steps were the same as those of Example 16.
[0520] Comparative Example 3 A lithium ion secondary battery was prepared by using a method substantially the same as that of Example 17, except that the prepared electrolyte composition was different, the first additive was omitted from the electrolyte, and the initial concentration of the electrolyte lithium salt remained unchanged. The remaining steps were the same as those of Example 17.
[0521] Comparative Example 4. A lithium ion secondary battery was prepared by using a method substantially the same as that of Example 1, except that the prepared electrolyte composition was different, the ethyl acetate of Formula I solvent in the electrolyte was replaced by propyl propionate, and the initial concentration of the electrolyte lithium salt remained unchanged. The remaining steps were the same as those of Example 1.
[0522] Comparative Example 5. A lithium-ion secondary battery was prepared by using a method substantially the same as that of Example 1, except that the electrolyte composition was different, ethyl acetate in the non-aqueous solvent was omitted from the electrolyte, and the initial concentrations of the first additive and the electrolyte lithium salt remained unchanged. The remaining steps were the same as those of Example 1.
[0523] Comparative Example 6 A lithium ion secondary battery was prepared by using a method substantially the same as that of Example 19, except that the prepared electrolyte composition was different, the first additive was omitted from the electrolyte, and the initial concentration of the electrolyte lithium salt remained unchanged. The remaining steps were the same as those of Example 19.
[0524] The relevant parameters of the above embodiments and comparative examples can also be found in Table 1-2.
[0525] 2. Test and analysis methods
[0526] 1. Conductivity of electrolyte
[0527] Use DDSJ-318 conductivity meter. Refer to page 5 of the industry standard HG / T4067-2015 "Lithium Hexafluorophosphate Electrolyte".
[0528] Test steps (density meter method):
[0529] Use a dry, clean, corrosion-resistant sample bottle to take about 100 mL of sample, seal it in a constant temperature water bath at 25℃±0.5℃, shake it from time to time, and when the sample temperature is constant, replace the sample bottle cap with a rubber stopper with an electrode. When the temperature is within the range of 25℃±0.5℃, read the data in the conductivity meter, which is the conductivity of the sample being tested.
[0530] 2. Initial DC internal resistance (DCR) test and DCR growth rate:
[0531] (1) Initial DC internal resistance (DCR0)
[0532] At 25°C, the battery to be tested is charged to 3.65V at a constant current of 0.5C, and then charged to a current of 0.05C at a constant voltage; the battery is discharged at a constant current of 0.5C for 30 minutes to adjust the battery to 50% SOC, at which time the battery voltage is recorded as U1; the battery is discharged at a constant current of 4C for 30 seconds, with a sampling point of 0.1 seconds, and the voltage at the end of discharge is recorded as U2. The discharge DCR of the battery at 50% SOC represents the initial DCR of the battery (recorded as DCR0), and the initial DCR0 of the battery = (U1-U2) / I, where I is the current corresponding to the 4C rate.
[0533] (2) DCR growth rate after cycling at 45°C
[0534] Example 1-8 and Comparative Example 1-5: At 45°C, the battery to be tested was charged to 3.65 V at a constant current of 1C, then charged at a constant voltage of 3.65 V until the current dropped to 0.05C, and after standing for 5 min, discharged to 2.1 V at a constant current of 1C. This is the first charge / discharge cycle of the battery, and the discharge capacity at this time is recorded as the discharge capacity of the first cycle of the battery (C1); Repeat the above steps for the same battery, and the process capacity of the battery after the nth cycle (Cn), the capacity retention rate after 500 cycles = C500 / C1×100%. Record the capacity retention rate after 500 cycles.
[0535] For Example 19 and Comparative Example 6, the test procedure is replaced as follows: at 45°C, the battery to be tested is charged to 3.65V at a constant current of 1C, then charged at a constant voltage of 3.65V until the current drops to 0.05C, left standing for 10 minutes, then discharged to 2.5V at a constant current of 1C, and left standing for 5 minutes. This is one charge and discharge cycle. Repeat the above steps for the same battery. Record the capacity retention rate after 500 cycles.
[0536] After the high temperature cycle performance test, the DCR is tested using the above method, recorded as DCR2, and the DCR growth rate = (DCR2-DCR0) / DCR0×100%.
[0537] The test results are recorded as "battery DCR0" and "DCR growth rate after 500 cycles at 45°C", please refer to Table 3-4.
[0538] 3. Fast charging time
[0539] The battery to be tested is charged and discharged for the first time at a current of 1C (i.e., the current value at which the theoretical capacity is completely discharged within 1 hour). The detailed steps include: at 35°C, the battery is charged at a constant current rate of 1C to a voltage of 3.65V, then charged at a constant voltage to a current ≤0.05C, left to stand for 5 minutes, and then discharged at a constant current rate of 0.33C to a voltage of 2.5V, and its actual capacity is recorded as C0. Then the battery is charged with constant current of 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, 3.0C0, 3.5C0, 4C0, 4.5C0, 5C0 in sequence to the full battery charge cut-off voltage of 3.65V or 0V negative electrode cut-off potential (whichever is reached first). After each charge is completed, it is necessary to discharge with 1C0 to the full battery discharge cut-off voltage of 2.1V. Record the corresponding negative electrode potential when charged to 10%, 20%, 30%, ..., 80% SOC at different charge rates. The charging rate-negative electrode potential curve under different SOC states is plotted, and the charging rate corresponding to the negative electrode potential of 0 V under different SOC states is obtained after linear fitting. The charging rate is the charging window under this SOC state, which is recorded as C(10% SOC), C(20% SOC), C(30% SOC), C(40% SOC), C(50% SOC), C(60% SOC), C(70% SOC), and C(80% SOC) respectively, and the maximum charging rate under the corresponding charge state, that is, the fast charging window, is obtained. The charging time from 10% to 80% is 6 / C(20%SOC)+6 / C(30%SOC)+6 / C(40%SOC)+6 / C(50%SOC)+6 / C(60%SOC)+6 / C(70%SOC)+6 / C(80%SOC), from which the charging time t0 of the battery under test from 10%SOC to 80%SOC can be calculated. The shorter the time t0, the better the fast charging capability of the battery under test.
[0540] Among them, SOC (State of Charge, when "SOC=0" means the battery is fully discharged, when "SOC=100%" means the battery is fully charged.
[0541] Exemplarily, “C(10% SOC)” corresponds to the charge rate obtained by linear fitting when the negative electrode potential is 0 V at 10% SOC.
[0542] The test results can be found in “Charging time t0” in Table 3.
[0543] 4. Cyclic performance test at high temperature (1C)
[0544] At 60°C (Examples 1-18 and Comparative Examples 1-5) or 45°C (Example 19 and Comparative Example 6), the battery to be tested was charged to 3.65 V at a constant current of 1C, then charged at a constant voltage of 3.65V until the current dropped to 0.05C, and after standing for 5 minutes, discharged to 2.1 V (Examples 1-18 and Comparative Examples 1-5) or 2.5V (Example 19 and Comparative Example 6) at a constant current of 1C. This is the first charge / discharge cycle of the battery, and the discharge capacity at this time is recorded as the discharge capacity of the first cycle of the battery (C1); repeat the above steps for the same battery, and the process capacity of the battery after the nth cycle (Cn), the capacity retention rate after n cycles = Cn / C1×100%. Record the number of cycles at which the cycle capacity retention rate is 80% (see Table 3) or record the capacity retention rate when the number of cycles is 600 (see Table 4).
[0545] The test results can be found in Table 3, “Number of cycles at 60°C for capacity decay to 80% SOC” and Table 4, “Capacity retention after 600 cycles at 45°C”.
[0546] The higher the number of cycles or capacity retention rate, the better the cycle life.
[0547] 5. Normal temperature cycle performance (25°C)
[0548] At 25°C, the battery to be tested is charged to 3.65V at 1C constant current, then charged to a cut-off current of 0.05C at 3.65V constant voltage, left for 10 minutes, and then discharged to 2.1 V (Examples 1-18 and Comparative Examples 1-5) or 2.5V (Example 19 and Comparative Example 6) at 1C constant current, left for 5 minutes. This is a charge and discharge cycle. The discharge capacity at this time is recorded as C0. Repeat this charge and discharge cycle process for the same battery, and record the discharge capacity C of the 1st, 2nd, ... nth rounds. n , where the number of cycles is at least 300.
[0549] Record the battery's cycle capacity retention rate P300 = C when the cycle is 300 cycles 300 / C0×100%.
[0550] The test results can be found in the "Capacity retention rate after 300 cycles at room temperature" in Table 4. The higher the test value, the better the room temperature cycle life.
[0551] 3. Test Analysis Results
[0552] Table 1.
[0553]
[0554] In Table 1, “F I " represents the initial mass proportion of the solvent of Formula I in the non-aqueous solvent.
[0555] “F A ” represents the initial mass proportion of the first additive in the electrolyte.
[0556] In Table 1, the additive contents expressed as percentages are the mass percentages in the electrolyte.
[0557] Table 2. Mass proportion of the first additive in the electrolyte before and after formation
[0558]
[0559] Table 3.
[0560]
[0561] Table 4.
[0562]
[0563] The conductivity of the electrolytes of Examples 1-19 at 25°C is in the range of 9 mS / cm to 25 mS / cm, and that of Examples 1-3, Examples 4-17 and Example 19 is in the range of 10 mS / cm to 18 mS / cm.
[0564] In the lithium-ion secondary batteries prepared by chemical formation, the battery cells were disassembled to test the electrolyte components: the mass proportions of the first additive in the electrolytes of Examples 1-19 were all in the range of 0.01%~3.2%; the mass proportions of the first additive in the electrolytes of Examples 1-7 and 10-19 were all in the range of 0.05%~1.6%; the mass percentages of various second additives in the electrolytes of Examples 1-19 were reduced to varying degrees and all still had residues.
[0565] The lithium-ion secondary batteries prepared in Examples 1-19 all have good fast-charging performance, extend the battery cycle life, and improve the battery fast-charging performance (extend the cycle life of the fast-charging battery). Please refer to Table 3-4.
[0566] Comparative Example 1 is relative to Example 1, Comparative Example 2 is relative to Example 16, Comparative Example 3 is relative to Example 17, and Comparative Example 6 is relative to Example 19. Comparative Examples 1-3 and 6 omit the first additive, resulting in a deterioration in the cycle life of the fast-charge battery.
[0567] Compared with Example 1, in Comparative Example 4, the ethyl acetate of Formula I solvent in the electrolyte is replaced with propyl propionate, and the internal resistance of the battery is significantly increased, and the fast charging capability and cycle life are seriously deteriorated.
[0568] Compared with Example 1, ethyl acetate in the non-aqueous solvent is omitted from the electrolyte of Comparative Example 3, the internal resistance of the battery increases significantly, and the fast charging capability and cycle life are seriously deteriorated.
[0569] The description of each embodiment and example above tends to emphasize the differences between each embodiment and example, and the same or similar parts can be referenced to each other. For the sake of brevity, this article will not repeat them. The technical features of the above-described embodiments and examples can be combined arbitrarily. For the sake of brevity, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0570] It should be noted that the present application is not limited to the above-mentioned embodiments and examples. The above-mentioned embodiments and examples are only examples. Within the scope of the technical solution of the present application, the embodiments and examples that have the same structure as the technical idea and play the same effect are all included in the technical scope of the present application. The above-described embodiments and examples only express several embodiments and examples of the present application, and the description is relatively detailed, but it cannot be understood as a limitation on the scope of the patent. In addition, without departing from the scope of the subject matter of the present application, various modifications that can be thought of by a person skilled in the art to the embodiments or examples, and other methods of combining some of the constituent elements in the embodiments or examples are also included in the scope of the present application.
Claims
1. A lithium ion secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein a separator is arranged between the positive electrode sheet and the negative electrode sheet; the electrolyte comprises an electrolyte salt, a non-aqueous solvent and an additive; the non-aqueous solvent comprises a chain carboxylate compound, the chain carboxylate compound comprises a solvent of formula I, and the structure of the solvent of formula I is shown in formula (I): In formula (I), R 11 and R 12 are each independently methyl or ethyl; The additives include a first additive and a second additive, wherein the first additive is a non-ionic organic additive containing a carbon-carbon triple bond, and the second additive is a negative electrode film-forming additive different from the first additive.
2. The lithium ion secondary battery according to claim 1, characterized in that: The chain carboxylic acid ester compound includes one or more of methyl formate, ethyl formate, methyl acetate and ethyl acetate.
3. The lithium ion secondary battery according to claim 1, characterized in that: The negative electrode plate includes a negative electrode active layer, the negative electrode active layer includes a negative electrode active material, and the average particle size of primary particles in the negative electrode active material is recorded as D1, wherein D1 is 0.1 μm to 2 μm.
4. The lithium ion secondary battery according to claim 3, characterized in that: The D1 of the negative electrode active material is 0.5 μm to 1.2 μm.
5. The lithium ion secondary battery according to claim 3, characterized in that: The negative electrode active material D v 50 is 5μm~18μm.
6. The lithium ion secondary battery according to claim 5, characterized in that: The negative electrode active material D v 50 is 6μm~15μm.
7. The lithium ion secondary battery according to claim 5, characterized in that: The negative electrode active material comprises a coated negative electrode material, wherein the coated negative electrode material comprises a negative electrode active body and a carbon coating layer located at least in a portion of the negative electrode active body.
8. The lithium ion secondary battery according to claim 7, characterized in that: The negative electrode plate meets one or more of the following characteristics: (a1) The mass proportion of the coated negative electrode material in the negative electrode active material is 80% to 100%; (a2) The coated negative electrode material includes coated graphite, the negative electrode active body in the coated graphite includes a graphite body, and the coated graphite accounts for 80% to 100% by mass of the negative electrode active material.
9. The lithium ion secondary battery according to any one of claims 3 to 8, characterized in that The positive electrode sheet comprises a positive electrode active layer, and the positive electrode active layer comprises a positive electrode active material; the positive electrode active material comprises one or more of a lithium-containing phosphate positive electrode material and a lithium transition metal oxide positive electrode material; The positive electrode sheet meets one or more of the following characteristics: (b1) The positive electrode active material includes a lithium-containing phosphate positive electrode material, and the D of the lithium-containing phosphate positive electrode material v 50: 0.3μm~2μm; (b2) The positive electrode active material includes a lithium transition metal oxide positive electrode material, and the D of the lithium transition metal oxide positive electrode material v 50 is 2μm~10μm.
10. The lithium ion secondary battery according to any one of claims 1 to 8, characterized in that The negative electrode plate comprises a negative electrode active layer, and the negative electrode active layer comprises a negative electrode active material; the positive electrode plate comprises a positive electrode active layer, and the positive electrode active layer comprises a positive electrode active material; (c1) D of the negative electrode active material v 1 greater than or equal to 1.5 μm; (c2) The positive electrode active material includes a lithium transition metal oxide positive electrode material, and the D of the lithium transition metal oxide positive electrode material v 10 greater than or equal to 1 μm; (c3) The positive electrode active material comprises a lithium-containing phosphate positive electrode material, and the D v 10 is greater than or equal to 0.2 μm.
11. The lithium ion secondary battery according to any one of claims 1 to 8, characterized in that: The negative electrode plate includes a negative electrode active layer, and the negative electrode active layer includes a negative electrode active material; the negative electrode active material includes at least one of a carbon-based material and a silicon-based material, and the mass proportion of the silicon-based material in the negative electrode active material is 0-40%.
12. The lithium ion secondary battery according to claim 11, characterized in that: The negative electrode plate meets one or more of the following characteristics: (d1) The mass proportion of the silicon-based material in the negative electrode active material is 0-25%; (d2) The silicon-based material includes a silicon-carbon composite material, which includes a porous carbon matrix and elemental silicon located in the pores of the porous carbon matrix; the mass proportion of the silicon-carbon composite material in the silicon-based material is 80% to 100%.
13. The lithium ion secondary battery according to any one of claims 1 to 8, characterized in that: The electrolyte satisfies one or more of the following characteristics: (e1) the mass percentage of the first additive in the electrolyte is 0.01% to 3.2%; (e2) The mass ratio of the second additive to the first additive is 0.01 to 50.
14. The lithium ion secondary battery according to claim 13, characterized in that: The electrolyte satisfies one or more of the following characteristics: (e1') the mass percentage of the first additive in the electrolyte is 0.05% to 1.6%; (e2′) The mass ratio of the second additive to the first additive is 0.1 to 30.
15. The lithium ion secondary battery according to any one of claims 1 to 8, characterized in that: The second additive includes one or more of a lithium salt additive, a phosphate ester additive, vinylene carbonate, a fluorocarbonate additive, a saturated sultone and a cyclic sulfate; The electrolyte satisfies one or more of the following characteristics: (f1) The lithium salt additive includes one or more of oxalate lithium salt, lithium tetrafluoroborate, lithium difluorophosphate and fluorosulfonic acid lithium salt; the oxalate lithium salt includes one or more of lithium difluorooxalatoborate, lithium difluorobisoxalatophosphate and lithium tetrafluorooxalatophosphate; the fluorosulfonic acid lithium salt includes one or more of lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide; (f2) the phosphate additive includes a silicon-based phosphate additive; the silicon-based phosphate additive includes one or more of tris(trimethylsilyl)phosphate and tris(trimethylsilyl)phosphite; (f3) The fluorocarbonate additive includes fluoroethylene carbonate; (f4) The cyclic sulfate ester includes one or more of monocyclic sulfate ester and polycyclic sulfate ester.
16. The lithium ion secondary battery according to claim 15, characterized in that: The electrolyte satisfies one or more of the following characteristics: (g1) the mass percentage of the lithium salt additive in the electrolyte is 0-3%; (g2) the lithium salt additive includes lithium difluorooxalate borate, and the mass percentage of lithium difluorooxalate borate in the electrolyte is 0-3%; (g3) The lithium salt additive includes lithium bis(fluorosulfonyl)imide; (g4) The mass percentage of the phosphate additive in the electrolyte is 0-2%; (g5) the mass percentage of the vinylene carbonate in the electrolyte is 0-3%; (g6) the mass percentage of the fluorocarbonate additive in the electrolyte is 0-10%; (g7) the fluorocarbonate additive includes fluoroethylene carbonate, and the mass percentage of fluoroethylene carbonate in the electrolyte is 0-10%; (g8) the mass percentage of the saturated sultone in the electrolyte is 0-3%; (g9) the mass percentage of the cyclic sulfate in the electrolyte is 0-3%; (g10) The cyclic sulfate ester includes a polycyclic sulfate ester, and the mass percentage of the polycyclic sulfate ester in the electrolyte is 0-3%.
17. The lithium ion secondary battery according to any one of claims 1 to 8, characterized in that: The electrolyte includes lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, and the molar volume concentration of the lithium bis(fluorosulfonyl)imide in the electrolyte is 0.01 mol / L to 0.5 mol / L.
18. The lithium ion secondary battery according to any one of claims 1 to 8, characterized in that: The electrolyte satisfies one or more of the following characteristics: (h1) the molecular weight of the first additive is less than or equal to 500 Da; (h2) the molecule of the first additive contains 1 to 4 carbon-carbon triple bonds; (h3) the carbon-carbon triple bond in the first additive is CH≡C-; (h4) The first additive includes one or more of a first alkynyl compound and a second alkynyl compound; wherein the first alkynyl compound contains a carbon-carbon triple bond and a Lewis base nitrogen heterocycle, the carbon-carbon triple bond and the Lewis base nitrogen heterocycle in the first alkynyl compound are connected by a linker L1, and the linker L1 contains a C covalently bonded to the carbon-carbon triple bond. 1-3 The second alkynyl compound contains a carbon-carbon triple bond and an alkyl carbonate group, the structure of the alkyl carbonate group is R2-OC(=O)-O-*, where * is a bonding site connected to a carbon atom, and R2 is C 1-3 The carbon-carbon triple bond in the second alkynyl compound and the alkyl carbonate group are connected by a linker L2, wherein the linker L2 contains a C covalently bonded to the carbon-carbon triple bond. 1-3 Alkylene.
19. The lithium ion secondary battery according to claim 18, characterized in that: The electrolyte satisfies one or more of the following characteristics: (i1) the molecular weight of the first additive is less than or equal to 300 Da; (i2) the first additive contains 1 to 4 Lewis base nitrogen heterocycles in its molecule; (i3) The Lewis base nitrogen heterocycle includes a substituted or unsubstituted imidazole group, wherein the imidazole ring in the substituted or unsubstituted imidazole group is substituted by 0, 1 or more substituent groups Q2, and the substituent groups Q2 in the substituted imidazole group are each independently C 1-3 an alkyl group, a cyano group or a fluorine atom; (i4) The first alkynyl compound is composed of a carbon-carbon triple bond, a C 1-3 Alkylene and -OC(=O)-R 10 Composition, R 10 is a Lewis base nitrogen heterocycle; the second alkynyl compound is composed of a carbon-carbon triple bond, C 1-3 Alkylene and -OC(=O)-OR 20 Composition, R 20 C 1-3 alkyl.
20. The lithium ion secondary battery according to claim 18, characterized in that: The first additive includes one or more of compound II and compound III; The structure of the compound II is Among them, L 11 C 1-3 Alkylene, Q2 is independently C 1-3 Alkyl, cyano or fluorine atom, p2 is 0, 1, 2 or 3; The structure of the compound III is Among them, L 21 C 1-3 Alkylene, R 22 C 1-3 alkyl.
21. The lithium ion secondary battery according to claim 20, characterized in that: The electrolyte satisfies one or more of the following characteristics: (j1) the first additive includes compound II, and the mass proportion of compound II in the first additive is 80% to 100%; (j2) The first additive includes a structure of The mass proportion of compound IIa in the first additive is 80% to 100%.
22. The lithium ion secondary battery according to any one of claims 1 to 8, characterized in that: The electrolyte satisfies one or more of the following characteristics: (k1) the mass proportion of the solvent of formula I in the chain carboxylic acid ester compound is 75% to 100%; (k2) the mass proportion of the chain carboxylic acid ester compound in the non-aqueous solvent is 5% to 80%; (k3) The conductivity of the electrolyte at 25° C. is 9 mS / cm to 25 mS / cm.
23. The lithium ion secondary battery according to claim 22, characterized in that: The electrolyte satisfies one or more of the following characteristics: (k1') the mass proportion of the solvent of formula I in the chain carboxylic acid ester compound is 90% to 100%; (k2') the mass proportion of the chain carboxylic acid ester compound in the non-aqueous solvent is 10% to 60%; (k3') The conductivity of the electrolyte at 25° C. is 10 mS / cm to 18 mS / cm.
24. A method for preparing a lithium ion secondary battery, characterized in that: The steps include: Placing an electrode assembly including a positive electrode sheet, a separator and a negative electrode sheet in a battery housing; wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet; An electrolyte is injected into the battery housing, and the electrolyte is allowed to stand to infiltrate the positive electrode sheet and the negative electrode sheet to form an electrolyte; wherein the electrolyte comprises an electrolyte salt, a non-aqueous solvent and an additive; the non-aqueous solvent comprises a chain carboxylic acid ester compound, the chain carboxylic acid ester compound comprises a solvent of formula I, and the structure of the solvent of formula I is shown in formula (I): In formula (I), R 11 and R 12 Each independently is a methyl group or an ethyl group; the first additive and the second additive, the first additive is a non-ionic organic additive containing a carbon-carbon triple bond, and the second additive is a negative electrode film-forming additive different from the first additive.
25. The method for preparing a lithium ion secondary battery according to claim 24, characterized in that: In the step of injecting electrolyte into the battery housing, the initial mass percentage of the first additive in the electrolyte is 0.1% to 5%.
26. The method for preparing a lithium ion secondary battery according to claim 24, characterized in that: In the step of injecting electrolyte into the battery housing, the initial mass percentage of the first additive in the electrolyte is 0.1% to 3%.
27. The method for preparing a lithium ion secondary battery according to any one of claims 24 to 26, characterized in that: A lithium ion secondary battery as claimed in any one of claims 2 to 23 is prepared.
28. An electrical device, characterized in that: The invention comprises at least one of the lithium ion secondary battery according to any one of claims 1 to 23 and the lithium ion secondary battery prepared by the method for preparing a lithium ion secondary battery according to any one of claims 24 to 26.
Citation Information
Patent Citations
Non-aqueous electrolyte for lithium secondary battery and lithium secondary battery comprising same
CN113711415A
Electrolyte and electrochemical device comprising same
CN114245947A
Battery cell, battery device, and electric device
CN119153758A
HIGH VOLTAGE ELECTROLYTE (Muldoon, Allred)
US20100209780A1
Novel battery systems based on two-additive electrolyte systems
US20190036171A1
Cited By
Secondary battery and electric device
CN120184179A
Battery cell, battery device and electric device
CN120565804A
Lithium ion battery and preparation method thereof, secondary battery and energy storage equipment
CN121885778A